HOMOGENEOUS BIOPOLYMER SUSPENSIONS, PROCESS FOR THE PRODUCTION THEREOF AND USES THEREOF - Patent application

JP2024501782A5Pending Publication Date: 2025-01-0711584022 CANADA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023563343
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-23
Filing Date
2021-12-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing methods for suspending insoluble and semi-soluble biopolymers in polar solvents often require chemicals, result in unstable suspensions with undesirable chemical residues, and do not achieve desired viscosity, homogeneity, stability, and particle size/shape.

Method used

A mechanical process involving high shear conditions in the presence of a polar solvent is used to create stable, homogeneous suspensions of insoluble and semi-soluble biopolymers, without the need for chemical additives, by subjecting biopolymers to mechanical energy to achieve desired particle sizes and shapes.

Benefits of technology

The process produces stable, homogeneous suspensions of biopolymers that are free of chemical residues, with controlled viscosity and particle characteristics, suitable for cosmetic and other commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Described herein is a homogeneous biopolymer suspension, its manufacturing process and its use. In an embodiment, the suspension is an aqueous suspension made from natural or biopolymers such as chitin, chitosan and cellulose. Described herein is a method and process for suspending these biopolymers in a polar solution by subjecting the biopolymer and polar solvent to high shear conditions, such as high mechanical energy. In an embodiment, the high shear conditions and / or high mechanical energy are provided by ball milling. The compositions and formulations of the present invention can find many applications, especially in the cosmetic industry, when formulated as pastes, ointments, creams or lotions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application is related to U.S. Provisional Patent Application No. 63 / 129,890, filed December 23, 2020, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to the field of biopolymers, more particularly to homogeneous suspensions containing insoluble or semi-soluble biopolymers, their production process and their use, especially in the cosmetics industry. [Background technology]

[0003] Natural polymers, or biopolymers, are abundant natural renewable polymers, making them an attractive source of commercial products. However, the most abundant biopolymers, such as cellulose and chitin, are insoluble, thereby limiting or complicating their use. Therefore, providing a means to suspend these biopolymers in polar solutions (e.g., aqueous solutions) would open up new commercial applications for these natural molecules, especially in the cosmetics industry. This industry requires constant innovation and is permanently searching for new natural, biocompatible, biodegradable and non-toxic ingredients.

[0004] Several methods and processes have been proposed to attempt to degrade biopolymers and / or to generate homogeneous biopolymer suspensions. Such methods and processes are described, for example, in PCT Publication No. WO 2020 / 036872 (e.g., starch) and WO 2020 / 024053 (e.g., chitin and chitosan), as well as U.S. Patent Application Publication No. 2004 / 0176477 (e.g., chitosan), JP 1986149237 (e.g., chitin) and JP 1986159430 (e.g., chitin and chitosan). The preparation of chitin nanofibers has also been described in the following scientific publications:Wu et al., BioMacromolecules(2014), dx.doi.org / 10.1021 / bm501416q;Wang et al., Carbohydrate Polymers(2017), dx.doi.org / 10.1016 / j.carbpol.2017.09.010;Drobrovol'skaya et al., Natural Polymers(2014), dx.doi.org / 10.1134 / S0965545X15010022;Zhu et al., Chemistry of Materials(2019), 31, 2078-2087;Ifuku and Saimoto, Nanoscale, 2012, 4, 3308;Lv et al. Food Hydrocolloids (2020), doi.org / 10.1016 / j.foodhyd.2020.106451.Also, the use ball milling to produce nanoparticles from biopolymers has been reported by Rochima et al., (Materials Science and Engineering, 193 (2017) 012043 doi: 10.1088 / 1757-899X / 193 / 1 / 012043), Wani, TA et al. (International Journal of Biological Macromolecules (2020), 154: 166-172), Piras, CC et al., Nanoscale Adv. (2019), 1: 937-947, Baheti, V. et al., World Journal of Engineering (2012), 9 (1): 45-50, Lin, H. et al. (Journal of Nano Research (2016), 40: 174-179), Kazemimostaghim, M (Powder Technology (2013), 241:230-235) and in patent publications CN 107151276, CN 112500584, CN 103980530, and CN 103316641. However, these methods and processes generally suffer from other problems because they require the presence of chemicals such as acids and / or bases, they require sonication or other techniques such as ultrasound, and / or the resulting products or suspensions are not ideal in terms of viscosity, uniformity, stability, shape and size of particles and fibers, the presence of undesirable chemical compounds, etc.

[0005] Thus, there is a need for suspensions made from homogeneous, stable, abundant, insoluble biopolymers. In particular, there is a need for biopolymer compositions that include biopolymer molecules that have been mechanically processed into a stable, homogeneous aqueous suspension. There is a related need for compositions that include biopolymer fibers having greater widths and / or greater lengths than those previously described.

[0006] There is also a need for simple and inexpensive methods and processes for obtaining such compositions and suspensions, especially methods and processes that do not require the addition of chemical compounds to avoid the presence of undesirable chemical compounds in the final product.

[0007] There is also a need for cosmetic compositions that are free of undesirable chemical compounds and that contain stable uniform suspensions made from abundant insoluble or semi-soluble biopolymers.

[0008] The present invention addresses these and other needs, as will become apparent from a review of the following disclosure and description of the features of the invention. Summary of the Invention

[0009] According to one aspect, the present invention relates to a biopolymer suspension comprising a suspension of nano-sized insoluble and / or semi-soluble particles (eg, fibers and / or aggregated spheres) stably dispersed in a polar solvent.

[0010] In another aspect, the present invention relates to a biopolymer composition comprising biopolymer molecules mechanically processed into a stable uniform suspension.

[0011] According to another aspect, the present invention relates to a biopolymer composition comprising a stable uniform suspension of insoluble and / or semi-soluble biopolymers in a polar solvent.

[0012] In another aspect, the present invention relates to a biopolymer composition comprising a stable uniform suspension of an insoluble biopolymer in a polar solvent.

[0013] According to another aspect, the present invention relates to a cosmetic composition comprising a biopolymer composition or a stable homogeneous suspension as defined herein.

[0014] According to another aspect, the present invention relates to a mechanical process for obtaining a biopolymer composition, comprising subjecting an insoluble and / or semi-soluble biopolymer to mechanical energy in the presence of a polar solvent to obtain a stable homogenous suspension of said insoluble and / or semi-soluble biopolymer.

[0015] According to another aspect, the present invention relates to a process for obtaining a biopolymer composition, comprising subjecting an insoluble and / or semi-soluble biopolymer to high shear conditions in the presence of a polar solvent until a change in state is observed and a stable homogenous suspension of the insoluble and / or semi-soluble biopolymer is obtained.

[0016] According to another aspect, the present invention relates to the use of a biopolymer suspension or a biopolymer composition as defined herein in the manufacture of a cosmetic composition.

[0017] According to another aspect, the present invention relates to the use of a biopolymer suspension or a biopolymer composition as defined herein in the manufacture of a seed coating, a surgical implant coating and / or as a food additive.

[0018] Further aspects, advantages and features of the present invention will become more apparent upon reading the following non-limiting description of preferred embodiments, which are illustrative and should not be construed as limiting the scope of the invention. [Brief description of the drawings]

[0019] In order that the invention may be readily understood, embodiments thereof are illustrated by way of example in the accompanying drawings, in which:

[0020] [Figure 1] FIG. 2 is a regime diagram illustrating the conditions under which viscosity is reduced and the desired changes in the formulation, according to one embodiment of the present invention.

[0021] [Diagram 2]1 is a bar graph showing the results of sizing analysis from SEM of particle size according to Example 3.

[0022] [Figure 3A] 1 is a bar graph showing the results of sizing analysis from SEM of fiber width according to Example 3.

[0023] [Figure 3B] 1 is a bar graph showing the results of sizing analysis from SEM of fiber length according to Example 3.

[0024] [Figure 3C] FIG. 1 shows the powder X-ray diffraction (pXRD) pattern of dried commercial chitin according to Example 3. [Figure 3D] 1 shows the powder X-ray diffraction (pXRD) pattern of Sample 3A according to Example 3. [Figure 3E] 1 shows the powder X-ray diffraction (pXRD) pattern of Sample 3B according to Example 3. [Figure 3F] 1 shows the powder X-ray diffraction (pXRD) pattern of Sample 3C according to Example 3. [Figure 3G] 1 shows the powder X-ray diffraction (pXRD) pattern of Sample 3D according to Example 3. [Figure 3H] 1 shows the powder X-ray diffraction (pXRD) pattern of Sample 3E according to Example 3. [Figure 3I] 1 shows the powder X-ray diffraction (pXRD) pattern of sample 3F according to Example 3.

[0025] [Figure 4] 1 is a scanning electron microscope (SEM) micrograph at 1000x magnification of dried chitin obtained from a chitin suspension according to Example 2.

[0026] [Diagram 5] 1 is a scanning electron microscope (SEM) micrograph at 1000x magnification of dried chitin obtained from a chitin suspension according to Example 2.

[0027] [Figure 6] 1 is a scanning electron microscope (SEM) micrograph at 30,000x magnification of dried chitin obtained from a chitin suspension according to Example 1.

[0028] [Figure 7] 1 is a scanning electron microscope (SEM) micrograph at 50,000x magnification of dried chitin obtained from a chitin suspension according to Example 1.

[0029] [Figure 8] 1 is a scanning electron microscope (SEM) micrograph at 30,000x magnification of dried chitin obtained from a chitin suspension according to Example 1.

[0030] [Figure 9] 1 is a line graph showing dynamic modulus results of suspended chitin at a chitin:water ratio of 0.75:20 according to Example 1.

[0031] [Figure 10] 1 is a scanning electron microscope (SEM) micrograph at 10,000x magnification of dried chitin obtained from the chitin suspension prepared according to Example 2.

[0032] [Figure 11] 1 is a line graph showing the dynamic modulus results of pretreated chitin suspensions having a chitin:water ratio of 1.5:20 according to Example 2.

[0033] [Figure 12A] 1 is a photograph of a clear plastic tube containing unground chitin according to Example 4. [Figure 12B] 1 is a photograph of a clear plastic tube containing suspended ground chitin according to Example 4.

[0034] [Figure 13A] 1 is a photograph of a clear plastic tube containing unmilled chitosan according to Example 4. [Figure 13B] 1 is a photograph of a clear plastic tube containing suspended, ground chitosan according to Example 4.

[0035] [Figure 14A] 1 is a photograph of a clear plastic tube containing unground alpha cellulose according to Example 4. [Figure 14B] 1 is a photograph of a clear plastic tube containing suspended, ground alpha cellulose according to Example 4.

[0036] [Figure 15A] 1 is a photograph of a transparent plastic tube containing unground cellulose fibers according to Example 4. [Figure 15B] 1 is a photograph of a transparent plastic tube containing suspended, ground cellulose fibers according to Example 4.

[0037] [Figure 16A] 1 is a photograph of a clear plastic tube containing unmilled microcrystalline alpha cellulose according to Example 4. [Figure 16B] 1 is a photograph of a clear plastic tube containing suspension-milled microcrystalline alpha cellulose according to Example 4.

[0038] [Figure 17A] 1 is a photograph of a clear plastic tube containing collagen without grinding according to Example 4. [Figure 17B] 1 is a photograph of a clear plastic tube containing suspended, ground collagen according to Example 4.

[0039] [Figure 18A] 1 is a photograph of a clear plastic tube containing unground silk according to Example 4. [Figure 18B] 1 is a photograph of a clear plastic tube containing suspended ground silk according to Example 4.

[0040] [Figure 19A]1 is a photograph of a clear plastic tube containing a suspended, ground mixture of chitin and chitosan according to Example 5. [Figure 19B] 1 is a photograph of a clear plastic tube containing a suspended, ground mixture of chitin and chitosan according to Example 5.

[0041] [Figure 20] 1 is a photograph of a clear plastic tube containing a suspended ground mixture of chitin and beeswax according to Example 6.

[0042] [Figure 21A] 1 is a photograph of a clear plastic tube containing a suspended ground mixture of chitin and vegetable oil according to Example 6. [Figure 21B] 1 is a photograph of a clear plastic tube containing a suspended ground mixture of chitin and vegetable oil according to Example 6. [Figure 21C] 1 is a photograph of a clear plastic tube containing a suspended ground mixture of chitin and vegetable oil according to Example 6.

[0043] [Figure 22] 1 is a photograph of a clear plastic tube containing a suspended ground mixture of chitin and soybean oil according to Example 6.

[0044] [Figure 23] 1 is a photograph of a clear plastic tube containing a suspended ground mixture of chitin and two solvents (glycerin + water) according to Example 7.

[0045] [Figure 24A] FTIR line graph of silk powder suspended and then dried according to Example 8.

[0046] [Figure 24B] 1 is a line graph of the FTIR of the cellulose powder that was suspended and then dried according to Example 8.

[0047] [Figure 24C]1 is a line graph of the FTIR of the collagen powder that was suspended and then dried according to Example 8.

[0048] [Figure 24D] 1 is a line graph of the FTIR of alginic acid powder that was suspended and then dried according to Example 8.

[0049] [Figure 24E] 1 is a line graph of the FTIR of the chitin powder that was suspended and then dried according to Example 8.

[0050] [Figure 24F] 1 is a line graph of FTIR of the suspended and dried chitosan powder according to Example 8.

[0051] [Figure 25A] 1 is a line graph of SSNMR of silk according to Example 8.

[0052] [Figure 25B] 1 is a line graph of SSNMR of cellulose according to Example 8.

[0053] [Figure 25C] 1 is a line graph of SSNMR of collagen according to Example 8.

[0054] [Figure 25D] 1 is a line graph of SSNMR of alginic acid according to Example 8.

[0055] [Figure 25E] 1 is a line graph of SSNMR of chitin according to Example 8.

[0056] [Figure 25F] 1 is a line graph of SSNMR of chitosan according to Example 8.

[0057] [Figure 26A]8 is a line graph of the PXRD of silk powder dried after suspension according to Example 8.

[0058] [Figure 26B] 8 is a line graph of the PXRD of the cellulose powder that was suspended and then dried according to Example 8.

[0059] [Figure 26C] 1 is a line graph of the PXRD of the suspended and dried collagen powder according to Example 8.

[0060] [Figure 26D] 8 is a line graph of the PXRD of suspended and dried alginic acid powder according to Example 8.

[0061] [Figure 26E] 8 is a line graph of the PXRD of the suspended and then dried chitin powder according to Example 8.

[0062] [Figure 26F] 1 is a line graph of the PXRD of suspended and dried chitosan powder according to Example 8.

[0063] [Figure 27A] 1 is a line graph of the transmittance of silk suspension according to Example 10. [Figure 27B] 1 is a line graph of the transmittance of a suspension of cellulose according to Example 10. [Figure 27C] 13 is a line graph of the transmittance of a collagen suspension according to Example 10. [Figure 27D] 1 is a line graph of the transmittance of an alginate suspension according to Example 10. [Figure 27E] 1 is a line graph of the transmittance of a suspension of chitin according to Example 10. [Figure 27F] 1 is a line graph of the transmittance of a suspension of chitosan according to Example 10.

[0064] [Figure 28A] Photograph of SEM imaging of alginate at 15 minutes according to Example 11. [Figure 28B] Photograph of SEM imaging of alginate at 15 minutes according to Example 11. [Figure 28C] Photograph of SEM imaging of alginate at 1 hour according to Example 11. [Figure 28D] Photograph of SEM imaging of alginate at 3 hours according to Example 11. [Figure 28E] Photograph of SEM imaging of alginate at 3 hours according to Example 11.

[0065] [Figure 29A] Photograph of SEM imaging of cellulose at 15 minutes according to Example 11. [Figure 29B] Photograph of SEM imaging of cellulose at 1 hour according to Example 11. [Figure 29C] Photograph of SEM imaging of cellulose at 3 hours according to Example 11. [Figure 29D] Photograph of SEM imaging of cellulose at 3 hours according to Example 11.

[0066] [Figure 30A] Photograph of SEM imaging of chitin at 15 minutes according to Example 11. [Figure 30B] Photograph of SEM imaging of chitin at 1 hour according to Example 11. [Figure 30C] Photograph of SEM imaging of chitin at 3 hours according to Example 11. [Figure 30D] Photograph of SEM imaging of chitin at 3 hours according to Example 11.

[0067] [Figure 31A] Photograph of SEM imaging of chitosan at 15 minutes according to Example 11. [Figure 31B] Photograph of SEM imaging of chitosan at 15 minutes according to Example 11. [Figure 31C]1 is a photograph of SEM imaging of chitosan at 1 hour according to Example 11. [Figure 31D] 1 is a photograph of SEM imaging of chitosan at 3 hours according to Example 11.

[0068] [Figure 32A] 1 is a photograph of SEM imaging of 15 minute silk according to Example 11. [Figure 32B] 1 is a photograph of SEM imaging of 15 minute silk according to Example 11. [Figure 32C] 1 is a photograph of SEM imaging of silk at 1 hour according to Example 11. [Fig. 32D] 1 is a photograph of SEM imaging of silk at 1 hour according to Example 11. [Figure 32E] 1 is a photograph of SEM imaging of silk at 3 hours according to Example 11. [Fig. 32F] 1 is a photograph of SEM imaging of silk at 3 hours according to Example 11. [Fig. 32G] 1 is a photograph of SEM imaging of silk at 3 hours according to Example 11.

[0069] [Diagram 33] 1 is a line graph showing the rheological polymer sweep of polymer suspensions and blends thereof according to Example 13.

[0070] [Diagram 34] 1 is a line graph showing the viscosity of pre-milled and non-pre-milled chitin according to Example 14.

[0071] [Figure 35A] The chemical structure of N-acetylglucosamine is shown.

[0072] [Figure 35B] 1 shows an estimate from ChemDraw™ of the 1H NMR spectrum of N-acetylglucosamine 1H NMR.

[0073] [Figure 36A] 1 shows 1H NMR spectra of two separate chitin suspensions according to Example 15. [Figure 36B] 1 shows 1H NMR spectra of two separate chitin suspensions according to Example 15.

[0074] [Figure 36C] 1H NMR spectra of N-acetylglucosamine standard (bottom) compared to chitin suspension #2 (top) according to Example 15.

[0075] [Figure 37A] 1 is a photograph showing unmilled ginseng powder in water according to Example 19. [Figure 37B] 1 is a photograph showing crushed and suspended carrots according to Example 19.

[0076] [Figure 38A] 1 is a graph showing particle size distribution of chitin milled at 200 RPM according to Example 23.

[0077] [Figure 38B] Photograph showing SEM imaging of chitin milled at 200 RPM for 180 minutes according to Example 23.

[0078] [Figure 39A] 2 is a graph showing particle size distribution of chitin milled at 400 RPM according to Example 23.

[0079] [Figure 39B] Photograph showing SEM imaging of chitin milled at 400 RPM for 180 minutes according to Example 23.

[0080] [Diagram 40] 2 is a graph showing particle size distribution of chitin without grinding according to Example 23.

[0081] [Diagram 41]2 is a graph showing particle size distribution of standard milled chitin according to Example 23.

[0082] [Figure 42A] 13 is a graph showing particle size distribution of chitosan milled at 200 RPM according to Example 23.

[0083] [Figure 42B] Photograph showing SEM imaging of chitosan milled at 200 RPM for 180 minutes according to Example 23.

[0084] [Figure 43A] 13 is a graph showing particle size distribution of chitosan milled at 400 RPM according to Example 23.

[0085] [Figure 43B] Photograph showing SEM imaging of chitosan milled at 400 RPM for 180 minutes according to Example 23.

[0086] [Diagram 44] 2 is a graph showing particle size distribution of chitosan without milling according to Example 23.

[0087] [Diagram 45] 2 is a graph showing particle size distribution of standard milled chitosan according to Example 23.

[0088] [Figure 46A] 2 is a graph showing particle size distribution of cellulose milled at 200 RPM according to Example 23.

[0089] [Figure 46B] Photograph showing SEM imaging of cellulose milled at 200 RPM for 180 minutes according to Example 23.

[0090] [Figure 47A] 2 is a graph showing particle size distribution of cellulose milled at 400 RPM according to Example 23.

[0091] [Figure 47B] Photograph showing SEM imaging of cellulose milled at 400 RPM for 180 minutes according to Example 23.

[0092] [Figure 48] 2 is a graph showing particle size distribution of cellulose without milling according to Example 23.

[0093] [Figure 49] 2 is a graph showing particle size distribution of standard milled cellulose according to Example 23.

[0094] [Figure 50] 13 is a line graph showing the viscosity of chitin suspensions containing emulsifiers, preservatives, and / or oils according to Example 27.

[0095] [Figure 51] 2 is a line graph showing the viscosity of cellulose suspensions containing emulsifiers, preservatives, and / or oils according to Example 27.

[0096] Further details of the present invention and its advantages will become apparent from the detailed description contained below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0097] In the following description of the embodiments, reference is made to the accompanying drawings, which are illustrative of examples in which the present invention can be implemented. It is understood that other embodiments can be made without departing from the scope of the disclosed invention. Unless otherwise defined, all technical and / or scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.

[0098] [General Overview] The present invention relates generally to the preparation of stable, uniform suspensions of insoluble and / or semi-soluble biopolymers in polar solvents. Related aspects relate to biopolymer compositions comprising such suspensions, their use for commercial applications such as cosmetics, and processes for obtaining the suspensions.

[0099] The inventors have discovered a means to suspend insoluble and / or semi-soluble biopolymers in polar solvents, thereby enabling useful commercial applications of these abundant natural molecules. The essence of the invention relies on subjecting the insoluble and / or semi-soluble biopolymers to mechanical energy in the presence of a polar solvent under conditions that result in a stable uniform suspension of the insoluble and / or semi-soluble biopolymers. In embodiments, the mechanical energy includes high shear conditions, and the viscosity of the suspension can be altered by varying these high shear conditions and the input material conditions.

[0100] [Biopolymer composition] One aspect of the present invention relates to a biopolymer composition that includes biopolymer molecules (eg, insoluble and / or semi-soluble) that have been mechanically processed into a stable homogenous aqueous suspension.

[0101] A related embodiment relates to a biopolymer composition comprising a stable uniform suspension of insoluble and / or semi-soluble biopolymers in a polar solvent.

[0102] As used herein, the term "homogeneous suspension" or "homogeneous composition" refers to a suspension or composition that appears to be homogeneous as determined by visual inspection. However, a suspension or composition can still qualify as "homogeneous" even if it contains particles of different dimensions or sizes (e.g., a range of particle sizes or lengths) or particles of different shapes (e.g., spherical particles, fibers, etc.). Preferably, a homogeneous suspension or homogeneous composition according to the present invention is also "stable", i.e., upon visual inspection, there is no or limited phase separation of its components over a period of hours, days, or weeks. A stable homogeneous suspension or homogeneous composition may show some solvent separation (e.g., depending on the biopolymer, solvent content, time elapsed since grinding, etc.), but typically does not show precipitation of solids from the suspension.

[0103] As used herein, the term "biopolymer" refers to a natural polymer produced by cells of an organism. Biopolymers consist of monomer units that are covalently linked to form larger molecules. The present invention encompasses water-insoluble or semi-soluble polypeptide, polysaccharide, and polynucleotide biopolymers as defined below. Other examples of biopolymers include natural rubber (a polymer of isoprene), suberin and lignin (complex polyphenol polymers), cutin and cutan (complex polymers of long-chain fatty acids), and melanin. In an embodiment, the biopolymer used as starting material and obtained in the suspension is substantially pure, i.e., consists only of purified natural polymers. Preferably, the biopolymer is substantially free of chemical residues, none of which is present or present in undetectable or trace amounts (see definition of "substantially free of chemical residues" below).

[0104] As used herein, the term "insoluble biopolymer" refers to a biopolymer that is "insoluble" in polar solvents (especially water), and this term encompasses equivalent terms such as "water insoluble" or "water insoluble" or "water insoluble" or "insoluble". Insolubility can typically be observed by separation, i.e., two distinct phases in an aqueous mixture, e.g., the biopolymer sediment / sediment at the bottom of the aqueous mixture or floats at the top of the aqueous mixture. According to the present invention, examples of insoluble biopolymers include, but are not limited to, chitin, chitosan, cellulose, hemicellulose, lignin, amylose, actin, fibrin, collagen, silk, fibroin, keratin, wool, alginic acid, and mixtures thereof.

[0105] As used herein, the term "semi-soluble biopolymer" refers to a biopolymer that can be solubilized in a polar solvent such as water but under certain conditions (e.g., molecular weight, heat, addition of chemicals such as acid, alcohol, detergent, etc.). According to the present invention, examples of semi-soluble biopolymers include, but are not limited to, gelatin, pectin, starch, amylopectin, agarose, hyaluronic acid, RNA, DNA, xanthan gum, latex, polymannan, suberin, cutin, cutan, and mixtures thereof.

[0106] As used herein, the terms "insoluble biopolymer" and "semi-soluble biopolymer" are meant to contrast with the term "soluble biopolymer", the latter referring to a biopolymer that can be solubilized in a polar solvent such as water. A biopolymer is considered soluble if no phase separation is observed between the biopolymer and the solvent in a mixture consisting essentially of the biopolymer and the solvent. The present invention relates to the use of insoluble and / or semi-soluble biopolymers and is not intended to encompass biopolymer suspensions made from soluble biopolymers. Examples of known soluble biopolymers (or biopolymer sources) that are excluded from the scope of the present invention include those that fail the phase separation test defined below.

[0107] Those skilled in the art will recognize that for a particular compound, the molecular weight may affect its solubility in a particular solvent, e.g., higher molecular weight biopolymers are typically less soluble than lower molecular weight biopolymers. Thus, according to the present invention, the same biopolymer can be classified into different categories (i.e., "insoluble," "semi-soluble," and "soluble"), and its molecular weight typically determines its behavior in the solvent (i.e., insoluble, semi-soluble, or soluble).

[0108] According to the present invention, it is envisaged to carry out a "phase separation test" to preliminarily identify the most suitable biopolymers for obtaining a biopolymer suspension according to the present invention, where polymers that phase separate are good candidates for obtaining a biopolymer suspension according to the present invention. In one embodiment, the phase separation test may involve combining the biopolymer in powder form with a desired solvent at standard temperature and pressure (STP), where the polymer either completely dissolves in the solvent (soluble), or partially dissolves or swells (semi-soluble), or does not dissolve and completely phase separates (insoluble).

[0109] Good candidates for obtaining a biopolymer suspension according to the present invention are biopolymers that pass the phase separation test, i.e. compounds that phase separate when mixed with a solvent. For example, pectin and gelatin typically fail the phase separation test, but lignin has been found to pass it occasionally depending on its source. Examples of biopolymers that fail the test, i.e. biopolymers that do not separate because they are already soluble, include, but are not limited to, sodium hyaluronate, sodium alginate, hydrolyzed collagen, carrageenan, guar gum, and xanthan gum. Without wishing to be bound by any theory, as shown above, solubility is likely dependent on the molecular weight of the biopolymer. Those skilled in the art will be able to identify insoluble and semi-soluble biopolymers useful in accordance with the current invention, taking into account this definition, the detailed description of the invention, and / or the numerous examples presented in the following exemplary section.

[0110] As noted above, the present invention encompasses mixtures of two, three, four, five or more insoluble biopolymers, including but not limited to chitin+chitosan, chitin+cellulose, chitin+collagen, chitin+silk, chitosan+silk, chitosan+cellulose, chitosan+collagen, cellulose+collagen, cellulose+silk, collagen+silk, etc. The present invention also encompasses mixtures of two, three, four, five or more semi-soluble biopolymers, including but not limited to agarose+DNA, xanthan gum+starch, latex+alginate, xanthan gum+DNA, guar gum+cutan, etc. Mixing two, three, four, five or more insoluble and semi-soluble biopolymers together may also be envisioned, including but not limited to chitin+agarose, chitosan+agarose, chitin+gelatin, chitin+xanthan gum, chitosan+xanthan gum, chitin+sodium hyaluronate, chitosan+sodium hyaluronate, cellulose+sodium hyaluronate, chitin+agarose, chitosan+agarose, cellulose+agarose, and the like.

[0111] According to the present invention, suitable solvents include those that can form hydrogen bonds between the solvent and the biopolymer, as greater hydrogen bonding capacity increases the stability of the suspension. Suitable solvents include polar protic solvents, polar aprotic solvents, and mixtures thereof.

[0112] In an embodiment, the solvent is a polar solvent that allows the biopolymer molecules to be suspended in a stable uniform suspension. In an embodiment, the solvent is a polar solvent that allows the biopolymer molecules to be suspended in a stable colloidal uniform suspension. The polar solvent may be a polar protic solvent or a polar aprotic solvent. The polar solvent may be an aqueous solvent. The present invention encompasses the use of two or more solvents of the same or different categories.

[0113] Conceivable examples of polar protic solvents that can be used include, but are not limited to, water, ethanol, propanol, methanol, glycerin, isopropanol, acetic acid, nitromethane, n-butanol, formic acid, isopropanol, 1-propanol, ethanol, methanol, acetic acid, water, glycerin, ethylene glycol, diethylene glycol, pentanol, cyclohexanol, hexanol, heptanol, octanol, 2-aminoethanol, benzyl alcohol, aniline, diethylamine, and mixtures thereof.In an embodiment, the polar protic solvent is water (e.g., distilled water).

[0114] Contemplated examples of polar aprotic solvents that can be used include, but are not limited to, acetone, ethyl acetate, acetonitrile, dimethylformamide, dimethylsulfoxide, hexamethylphosphoramide, dichloromethane, dimethylpropyleneurea, hexamethylphosphortriamide, tetrahydrofuran, dimethylsulfoxide, acetylacetone, ethyl acetoacetate, benzonitrile, pyridine, diglyme, ethyl benzoate, methoxybenzene, tetrahydrofuran, pentanone, methyl acetate, ether, and mixtures thereof.

[0115] Contemplated examples of aqueous solvents that can be used include, but are not limited to, water, ethanol, propanol, methanol, glycerin, and the like, and mixtures thereof. In embodiments, the solvent is water (e.g., distilled water). Additionally, numerous examples of potentially useful polar protic solvents and dipolar aprotic solvents are provided below.

[0116] Those skilled in the art will be able to identify the solvent that best suits a particular use.For example, some solvents may be less preferred than others because they may not be safe for human application.Similarly, ethanol and propanol may be useful, for example, in hand sanitizers but not in face creams, and solvents such as ethyl acetate, acetonitrile, dimethylformamide, dimethylsulfoxide, etc. may be useful in industrial applications but not necessarily in human or cosmetic applications.

[0117] The nano-sized insoluble and / or semi-soluble particles present in the biopolymer suspension according to the invention may be in the form of fibers and / or aggregated spheres or solids. In an embodiment, the biopolymer suspension comprises particles having a shape similar to the particles shown in any of Figures 4-8, 10, 28A-28E, 29A-29D, 30A-30D, 31A-31D, 32A-32G, 38B, 39B, 42B, 43B, 46B, and 47B.

[0118] Without being bound by any theory, it is hypothesized that higher shear forces (e.g., higher milling power, longer milling time, etc.) cause the original biopolymer molecules (usually found in the form of fibers) to become smaller biopolymer molecules (e.g., spheroids), with the fibers typically being larger than the spheroids. For example, there may be a first defibrillation step in which the fibers separate from each other so that they become thinner and shorter. Furthermore, in this process, the fibers become much shorter and can aggregate into spheres, especially upon drying. Thus, according to the present invention, it is conceivable to obtain a biopolymer suspension containing particles of a desired shape or size by controlling the shear forces applied to the original biopolymer molecules (e.g., the speed of milling, the milling power, the number and / or size of the balls). Further factors or conditions that may affect the shape and size of the particles in the final suspension include, but are not limited to, the source or identity of the starting material, the initial particle size, the amount of material, the solvent, the additives, the number and / or size of the balls in the case of the grinder, etc. Thus, in embodiments, the invention encompasses varying or controlling one or more of these parameters and / or shear conditions (e.g., grinding conditions) to alter the shape and / or size of particles in the biopolymer suspension. It is also envisioned that cryo-SEM can be performed to image the composition or suspension in a pseudo-wet (frozen) state to obtain information about how the particles look in suspension, and these images can be compared to images in the dried form to further visualize the preparation of particles (e.g., fibers, spheres) with desired properties (e.g., size, diameter, length, etc.) and optimize accordingly.

[0119] In an embodiment, the uniform suspension is a colloidal uniform suspension. In an embodiment, the colloidal uniform suspension includes colloids having a size range of about 1 nm to about 1 μm.

[0120] In an embodiment, the stable homogenous suspension comprises biopolymer fibers having a width of about 7 nm to about 5 μm, or about 10 nm to about 5 μm, or about 20 nm to about 5 μm, or about 25 nm to about 5 μm, or about 30 nm to about 5 μm, or about 35 nm to about 5 μm, or about 35 nm to about 3 μm.

[0121] In embodiments, the stable uniform suspension comprises biopolymer fibers having a width of at least 10 nm, or at least 20 nm, or at least 30 nm, or at least 40 nm, or at least 50 nm, or at least 75 nm, or at least 100 nm, or at least 250 nm, or at least 500 nm, or at least 750 nm, or at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm, or at least 10 μm or greater.

[0122] In embodiments, the stable homogenous suspension comprises biopolymer fibers having a length of about 50 nm to about 10 μm, or about 100 nm to about 10 μm, or about 500 nm to about 10 μm, or about 750 nm to about 10 μm, or about 800 nm to about 10 μm, or about 900 nm to about 5 μm, or about 1 μm to about 10 μm, or about 1 μm to about 5 μm, or about 1 μm to about 3 μm.

[0123] In embodiments, the stable uniform suspension comprises biopolymer fibers that are at least 50 nm, or at least 100 nm, or at least 250 nm, or at least 500 nm, or at least 750 nm, or at least 800 nm, or at least about 900 nm, or at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm, or at least 6 μm, or at least 7 μm, or at least 8 μm, or at least 9 μm, or at least 10 μm or longer.

[0124] In embodiments, the stable homogenous suspension has a width of greater than 20 nm (e.g., at least 25 nm, or at least 40 nm, or at least 50 nm) and a length of greater than 50 nm (e.g., at least 100 nm, or at least 500 nm, or at least 1 μm, or at least 2 μm); or (ii) a width of greater than 32 nm (e.g., at least 35 nm, or at least 40 nm, or at least 50 nm) and a length of greater than 50 nm (e.g., at least 100 nm, or at least 500 nm, or at least 1 μm, or at least 2 μm); or (iii) a width of greater than 20 nm (e.g., at least 25 nm, or at least 40 nm, or at least 50 nm) and a length of greater than 500 nm (e.g., at least 600 nm, or at least 750 nm, or at least 1 μm, or at least 2 μm); or (iv) a width of greater than 30 nm (e.g., at least 35 nm, or at least or (v) a width of more than 8 nm (e.g., at least 10 nm, at least 25 nm, or at least 35 nm, or at least 40 nm, or at least 50 nm) and a length of more than 340 nm (e.g., at least 350 nm, or at least 500 nm, at least 750 nm, or at least 900 nm, or at least 1 μm, or at least 2 μm); or (vi) a width of more than 11 nm (at least 15 nm, at least 25 nm, or at least 35 nm, or at least 40 nm, or at least 50 nm) and a length of more than 166 nm (e.g., at least 200 nm, or at least 350 nm, or at least 500 nm, at least 750 nm, or at least 900 nm, or at least 1 μm, or at least 2 μm);or (viii) comprises biopolymer fibers having both a width greater than 32 nm (e.g., at least 35 nm, or at least 40 nm, or at least 50 nm) and a length greater than 800 nm (e.g., at least 900 nm, or at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm);

[0125] In embodiments, the stable homogenous suspension comprises biopolymer fibers in which the average width and average length of the fibers in the suspension are as defined above, e.g., an average width of greater than 20 nm (e.g., at least 25 nm, or at least 40 nm, or at least 50 nm) and an average length of greater than 50 nm (e.g., at least 60 nm, at least 75 nm, or at least 100 nm, or at least 500 nm, at least 750 nm, or at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm).

[0126] In embodiments, the stable uniform suspension comprises biopolymer fibers having both crystalline and amorphous regions. In embodiments, the stable uniform suspension comprises biopolymer fibers having a spherical shape. In embodiments, the stable uniform suspension is composed primarily or exclusively of suspended biopolymer nanofibrils.

[0127] Those skilled in the art recognize that particle size measurements can vary depending on the measurement method and the state of the particles (e.g., particles in a wet state are larger than the same particles in a dry state). Typically, particles are in a wet or suspended state when measured by dynamic light scattering (DLS), and in a dry state when measured by scanning electron microscopy (SEM).

[0128] In an embodiment, a biopolymer suspension or composition according to the invention comprises spherical particles and aggregates, the particle size ranges as measured by dynamic light scattering (DLS) are as set out in Table 3 below.

[0129] In embodiments, the biopolymer suspension or composition comprises aggregated spheres of alginate having an average size of about 40 nm to about 80 nm, or about 45 nm to about 75 nm, as measured by scanning electron microscopy (SEM). In embodiments, the stable homogenous suspension comprises aggregated spheres of alginate having a median diameter of about 30 nm to about 70 nm, or about 35 nm to about 65 nm, and an average size of about 40 nm to about 80 nm, or about 45 nm to about 75 nm, as measured by scanning electron microscopy (SEM).

[0130] In embodiments, the biopolymer suspension or composition comprises agglomerated spheres of cellulose having an average size of about 50 nm to about 80 nm, or about 55 nm to about 75 nm, or an average size of about 40 nm to about 80 nm, or about 45 nm to about 75 nm, as measured by scanning electron microscopy (SEM). In embodiments, the stable homogenous suspension comprises agglomerated spheres of cellulose having a median diameter of about 35 nm to about 75 nm, or about 40 nm to about 65 nm, and an average size of about 40 nm to about 80 nm, or about 45 nm to about 75 nm, as measured by scanning electron microscopy (SEM).

[0131] In embodiments, the biopolymer suspension or composition comprises agglomerated spheres of chitin having an average size of about 45 nm to about 85 nm, or about 50 nm to about 80 nm. In embodiments, the stable homogenous suspension comprises agglomerated spheres of cellulose having a median diameter of about 45 nm to about 80 nm, or about 50 nm to about 75 nm, as measured by scanning electron microscopy (SEM).

[0132] In embodiments, the biopolymer suspension or composition comprises agglomerated spheres of chitosan having an average size of about 75 nm to about 120 nm, or about 80 nm to about 115 nm, or about 85 nm to about 110 nm, as measured by scanning electron microscopy (SEM). In embodiments, the stable homogenous suspension comprises agglomerated spheres of chitosan having a median diameter of about 70 nm to about 100 nm, or about 75 nm to about 95 nm, as measured by scanning electron microscopy (SEM).

[0133] In embodiments, the biopolymer suspension or composition comprises silk aggregated spheres having an average size of about 40 nm to about 165 nm, or about 45 nm to about 160 nm, as measured by scanning electron microscopy (SEM). In embodiments, the stable homogenous suspension comprises silk aggregated spheres having a median diameter of about 40 nm to about 150 nm, or about 45 nm to about 140 nm, as measured by scanning electron microscopy (SEM).

[0134] In an embodiment, a biopolymer suspension or composition according to the invention comprises one or more particles of alginate, cellulose, chitin, chitosan and silk, wherein the particle size range as measured by SEM is as defined in Table 4 below (e.g., Example 11), or as defined in any of Tables 30-44 below (e.g., Example 23), or as shown in any one of Figures 38A, 39A, 40, 41, 42A, 43A, 44, 45, 46A, 47A, 48 and 49 (e.g., Example 23).

[0135] In embodiments, the biopolymer suspension or composition is characterized by visual properties as shown in the SEM images shown in any one of Figures 28A-32G (e.g., Example 11) or any one of Figures 38B, 39B, 42B, 43B, 46B and 47B (e.g., Example 23).

[0136] In embodiments, the biopolymer suspension or composition is characterized by a Fourier transform infrared spectroscopy (FTIR) spectrum shown in any one of Figures 24A-24F (eg, Example 8).

[0137] In embodiments, the biopolymer suspension or composition is characterized by solid state nuclear magnetic resonance characterization (SSNMR) as shown in any one of Figures 25A-25F (eg, Example 8).

[0138] In embodiments, the biopolymer suspension or composition is characterized by a powder X-ray diffraction (PXRD) pattern as shown in any one of Figures 26A-26F (eg, Example 8).

[0139] In embodiments, the biopolymer suspension or composition is characterized by dynamic light scattering (DLS) measurements as reported in Table 3 (eg, Example 9).

[0140] In embodiments, the biopolymer suspension or composition is characterized by the transmittance spectrum shown in any one of Figures 27A-27F (eg, Example 10).

[0141] In embodiments, the biopolymer suspension or composition is characterized by a sweep suspension test as reported in Table 5 (eg, Example 12) or as shown in FIG. 33 (eg, Example 13).

[0142] In embodiments, the biopolymer suspension or composition is characterized by the rheological behavior as shown in FIG. 34 (eg, Example 14).

[0143] Advantageously, the stable homogenous suspensions of the present invention are very stable, i.e., the biopolymers (e.g., fibers, spherules) do not settle to the bottom. In embodiments, the insoluble and / or semi-soluble biopolymers remain in suspension for at least 1 week, or at least 1 month, or at least 6 months, or at least 12 months, or at least 18 months, or at least 2 years, or at least 3 years or longer.

[0144] As shown in Figure 1 and described later herein, it is possible to vary the viscosity of compositions and suspensions according to the present invention. Indeed, the viscosity can be varied such that the biopolymer composition has the viscosity of what is commonly referred to as a paste, ointment, cream, lotion, gel, or milk. In embodiments, stable homogenous suspensions include viscosities of about 25 mPa to about 85,000 mPa.

[0145] In an embodiment, the biopolymer composition or suspension is substantially pure and consists essentially of biopolymer and polar solvent (e.g., water). Thus, such a composition or suspension is advantageously substantially free of any chemical residues and other chemicals that may be required in the prior art to produce a suspension containing a biopolymer. As used herein, "substantially free of chemical residues" means that chemical compounds such as acids, bases, reactive chemicals, organic and / or inorganic salts, surfactants, dispersants (e.g., Twin 80™), silanizing reagents, acrylamides, etc., are not present in the final composition or suspension, or are present only in undetectable or trace amounts. In an embodiment, the biopolymer constitutes at least 98%, or at least 99%, or at least 99.9%, or at least 99.99% (by weight) of the organic compounds of the biopolymer composition or suspension, i.e., the biopolymer composition or suspension contains less than 2%, or less than 1%, or less than 0.1%, or less than 0.01%, or less than 0.001% (by weight) of organic components other than the biopolymer or degradation products.

[0146] The biopolymer composition or suspension may also include one or more additives. A non-limiting list of additives includes preservatives, stabilizers and emulsifiers (e.g., cetyl alcohol, glyceryl stearate, soy butter, PC90, tara gum, PSC3, PEG, guar, xanthan gum, agarose, sodium hyaluronate, Tween 80 (trademark), glycerin (humectant), thickeners, dyes, powders (e.g., mica, pigments, chalk), inks, colorants, fragrances, essential oils, extracts (e.g., plant extracts such as aloe vera), vitamins (e.g., ascorbic acid), acids (e.g., acetic acid, citric acid, stearic acid), oils (cocoa butter, emulsifier oil, olive oil, shea butter, silicone oil, mineral oil), metal oxides (e.g., zinc oxide), salts (e.g., sea salt, sodium lactate), honey, clay, propenyl glycol, polyethylene glycol, dry ingredients (e.g., rose petal powder, orange peel powder, chamomile flowers, calendula petals, etc.), allantoin, acetyl glucosamine (GlcNA c), waxes (e.g., beeswax), peptides and proteins, pharmaceutical compounds (e.g., N-acetylglucosamine, lidocaine, capsaicin, baclofen, ketamine, methylsulfonylmethane, orphenadrine, tetracaine, amitriptyline, bupivacaine, cyclobenzaprine, doxepin, gabapentin, guaifenesin, acetaminophen, ibuprofen, naproxen, diclofenac, meloxicam, piroxicam, ketoprofen, any NSAID), sugars (e.g., glucose, fructose, galactose, etc.), any monomer of cellulose, starch, chitin, chitosan, alginic acid, collagen, silk, etc. Additives can be added before, during and / or after the step of high shear conditions and / or high mechanical energy.

[0147] In an embodiment, the additive or stabilizer is selected from the following stabilizers: agar, sodium alginate, carrageenan, guar, konjac, tragacanth, locust bean gum, psyllium, tara gum, fenugreek gum, xanthan gum, abietic acid, acetyl mannosyl erythritol lipid, acrylamide / sodium acryloyldimethyltaurate copolymer, acrylates / aminoacrylates / C10-30 alkyl PEG-20 itaconate copolymer, acrylates / C10-30 alkyl acrylate crosspolymer. , Acrylates / C5-8 Alkyl Acrylate Copolymer, Acrylates / Stearyl Methacrylate Copolymer, Acrylates / Vinyl Isodecanate Crosspolymer, Acrylates / Vinyl Neodecanoate Crosspolymer, Acrylic Acid / Stearyl Acrylate Copolymer, Acrylic Acid / Stearyl Methacrylate / Dimethicone Methacrylate Copolymer, Bisacryloyl Poloxamer, Alcaligenes Polysaccharide, Alcohol C9-11, Allyl Methacrylate Crosspolymer, Sweet Almond Oil Polyglyceryl-4 Ester, Behenic Acid Aluminum, Aluminum Caprylate, Aluminum Dicetyl Phosphate, Aluminum Dilinoleate, Aluminum Dimyristate, Aluminum Distearate, Aluminum Isostearate, Aluminum Isostearate / Laurate / Palmitate, Aluminum Isostearate / Laurate / Stearate, Aluminum Isostearate / Myristate, Aluminum Isostearate / Palmitate, Aluminum Isostearate / Stearate, Aluminum Lanolinate, Aluminum Monostearate, Aluminum Myristate, Aluminum Myristic Acid / Palmitate, Aluminum / Magnesium Stearate Hydroxide, Ammonium Acryloyldimethyltaurate / Methacrylate Steareth-25 Methacrylate Crosspolymer, Ammonium Acryloyldimethyltaurate / Steareth-8 Methacrylate Copolymer, Ammonium Acryloyldimethyltaurate / Vinylformamide Copolymer, Ammonium Alginate, Ammonium Phosphatidyl Lapecinate, Ammonium Polyacryloyldimethyltaurate, Ammonium Sherasinate,Amodimethicone Glycerol Carbamate, AMP-C8-18 Perfluoroalkylethyl Phosphate, Aphanotes Sacrum Polysaccharide, Arachidyl Alcohol, Tragacanth Gum, Tragacanthus Root Extract, Avocadamide DEA, Babasci Acid, Crosslinked Bacillus / Glucose / Sodium Glutamate Ferment, Dextrin, Batyl Alcohol, Hydrolyzed Beeswax, Synthetic Beeswax, Behenyl Alcohol, Bentonite, Benzalkonium Montmorillonite, Benzalkonium Sepiolite, Bitan Emulsion stabilizer, brassica alcohol emollient, brassicyl isoleucine esylate, butenediol / vinyl alcohol copolymer, butoxyhydroxypropyl cetyl hydroxyethylcellulose, butter decyl esters, butyl acrylate / isopropylacrylamide / PEG-18 dimethacrylate crosspolymer, butyl babasticate, butylene glycol cocoate, butylene glycol isostearate, C1-5 alkyl galactomannan, C12-13 alcohol, C12-14 sec-palace-3, C12-14 sec-palace-5, C12-14 sec-palace-7, C12-14 sec-palace-8, C12-14 sec-palace-9, C12-14 sec-palace-12, C12-14 sec-palace-15, C12-14 sec-palace-20, C12-14 sec-palace-30, C12-14 sec-palace-40, C12-14 sec-pareth-50, C12-15 alcohol, C12-16 alkyl peg-2 hydroxypropyl hydroxyethyl cellulose, C12-18 alkyl glucoside, hydrogenated C12-18 triglyceride, C14-15 alcohol, C14-18 glycol, C14-22 alcohol, C15-18 glycol, bis-C16-18 alkyl glyceryl undecyl dimethicone, C18-22 alkyl peg-25 methacrylate / diethylaminoethyl methacrylate copolymer, C18-30 glycol, C18-38 alkyl hydroxystearoyl stearate, C20-22 alcohol, C20-30 glycol, C20-40 alcohol, C20-40 alkyl crylene, C22-24 pareth-33, bis-C24-28 hydroxyalkyl olivoyl glutamate, C28-52 olefin / undecylenic acid copolymer,C30-50 Alcohol, Calcium Carboxymethylcellulose, Calcium Carrageenan, Calcium Laurate, Calcium Myristate, Calcium Polyglutamate Crosspolymer, Calcium Potassium Carbomer, Calcium Saccharate, Calcium Starch Octenylsuccinate, Calcium Stearate, Calitris Tetravalent Resin, Candelilla Wax, Candelilla / Jojoba / Rice Bran Polyglyceryl-3 Esters, Hemp Seed Oil Glycereth-8 Esters, Caprylyl Dimethicone Ethoxyglucoside, Caprylyl / Capryl Wheat Bran / Wheat Glycoside, Carbomer 934, Carboxymethylcellulose Acetate Butyrate, Carboxymethyl Hydroxyethylcellulose, Carboxymethyl Hydroxypropyl Guar, Carnauba Wax, Carthamus Tinctorius Extract, Hydrogenated Castor Oil Behenyl Ester, Castor Oil Phosphate, Hydrogenated Castor Oil Stearyl Ester, Hydrogenated Castor Oil / Sebacic Acid Copolymer, Capric / Caprylic Acid, Cellulose Acetate Propionate Carboxylate, Hydrolyzed Cellulose Gum, Cellulose Microcrystals, Ceramide NS / PEG-8 / Succinic Acid Copolymer, Ceratonia Siliqua Gum, Ceresin, Ceteareth-6 Olivate, Cetostearyl Alcohol, Cetyl Alcohol, Cetyl Dimethicone PEG-7 Acetate, Cetyldodecyl Succinate, Cetyl Hydroxyethylcellulose, Cetyl PEG / PPG-7 / 3 Dimethicone, Bis-Cetyl / PEG-8 Cetyl PEG-8 Dimethicone, Chitosan Laura Myrosuccinimide, chitosan lauroyl glycinate, cholesterol / hdi / pullulan copolymer, citrus aurantium dulcis peel extract, citrus aurantium sinensis fiber, cocamide, cocamide DEA, cocamide MEA, cocamide MIPA, cocamidopropyl lauryl ether, cocoa butter glyceryl esters, coconut alcohol, coconut oil methylpropanediol esters, hydrolyzed corn starch hydroxyethyl ether, guar (cyamopsis tetragonoloba gum), decyl castorate, decyl glucoside, decyl hemp cedate, 7-dehydrocholesterol, dehydroxanthan gum, sodium dicapryl sulfosuccinate,Diethylene glycol / hydrogenated dimer dilinoleic acid copolymer, digalactosyl glyceryl linoleate / palmitate / oleate, diglycerin / dilinoleic acid / hydroxystearic acid copolymer, dihydrolanosterol, dihydroxyethyl cocamine oxide, dihydroxyethyl lauramine oxide, diisotridecyl lauroyl glutamate, dilauryl maleate / C20 olefin copolymer, dimaltosyl cyclodextrin, hydrogenated dimer dilinoleyl / dimethyl carbonate copolymer, dimethicone crosspolymer, di Methicone Ethoxyglucoside, Dimethicone / Lauryl Dimethicone / Bis-Vinyl Dimethicone Crosspolymer, Dimethicone / PEG-15 Crosspolymer, Dimethylcapramide, Dimethylcocamine, Dimethyllauramine Isostearate, Dioleyl Phosphate, Dipropylene Glycol Isobornyl Ether, Dodecyl Hexadecanol, Bis-Ethoxydiglycol Cyclohexane 1,4-Dicarboxylate, Ethyl Hydroxyethylcellulose, Bis-Ethyl PPG-Behenate, Dimonium Methosulfate, Bis-(Ethyl PPG-3 Behenate) Dimethylaminopropanediol, Sodium Hyaluronate ... Mononium Methosulfate, Ethylene Vinyl Acetate Copolymer, Ethylene / Acrylic Acid Copolymer, Ethylene / Sodium Acrylate Copolymer, Feruloyl Soy Glyceride, Perfluorocyclohexylmethanol, Perfluoroheptane, Perfluoromethylcyclohexane, Perfluoromethyldecalin, Gum Ghatti, Glucose Pentaacetate, Alpha-Dextro-Glucose Pentaacetate, Glycereth-7 Malate, Glycereth-8 Hydroxystearate, Glycereth-7 Benzoate, Hydrogenated Glyceryl Abieate, Glycol Cetearate, Acetylated Glycol Stearate, Glycosyl Trehalose, Grape Seed Oil Glycereth-8 Ester, Grape Seed Oil Polyglycerin-6 Ester, Maleated Hexene / Propylene Copolymer, Hydroxyquinoline Sulfate, Hydroxyapatite, Hydroxybutyl Methylcellulose, Bis-Hydroxyethoxypropyl Dimethicone Beeswax Ester, Bis-Hydroxyethoxypropyl Dimethicone Isostearate, Hydroxyethyl Acrylate / Sodium Acryloyldimethyltaurate Copolymer,Hydroxyethyl cellulose, hydroxyethyl isostearyloxyisopropanolamine, hydroxypropyl cellulose, hydroxypropyl guar gum, hydroxypropyl methylcellulose, hydroxypropyl xanthan gum, hydroxypropyltrimonium inulin, hydroxypropyltrimonium xanthan gum, hydroxystearic / linolenic / linolenic / oleic polyglyceride, hydroxystearic / linolenic / oleic polyglyceride, lauryl carbamate inulin, synthetic Japan wax, jojoba oil glycereth-8 ester, hydrogenated lanolin alcohol, lanolinamide DEA, lauryl alcohol, lauryl alcohol diphosphonate, lauryl dodecenyl succinate, lauryl / myristyl wheat bran / straw glycosides glycosides), hydrogenated lime seed oil, alginate, magnesium laurate, maltitol, maltodextrin, methoxypeg-22 / dodecyl glycol copolymer, methoxypeg / ppg-25 / 4 dimethicone, methylcellulose, methyl vinyl ether-maleic anhydride copolymer, montmorillonite, myristyl / palmitamide butylguanidine acetate, myristyl alaninate, myristyl alcohol, oleic acid / linoleic acid / linolenic polyglyceride, olive alcohol, hydrogenated olive oil caprylyl ester, hydrogenated olive oil cetyl ester, hydrogenated olive oil decyl ester, hydrogenated olive oil hexyl ester, hydrogenated olive oil lauryl ester, hydrogenated olive oil bean oil myristyl ester, hydrogenated olive oil stearyl ester, hydrogenated orange seed oil, ozokerite, palm kernel amide DEA, palm kernel amide MEA, palm kernel amide MIPA, palmamide DEA, palmamide MEA, palmamide MIPA, peanut amide MEA, peanut amide MIPA, pectin, tris(PEG-2 phenylalanylcarboxamide)cyclohexane, PEG-2 tallow amide DEA, PEG-4 PEG-12 dimethicone, PEG-5 pentaerythrityl dimethylolpropionate-2 dendrimer, PEG-5 pentaerythrityl dimethylolpropionate-3 dendrimer, PEG-5 pentaerythrityl dimethylolpropionate-4 dendrimer,PEG-7 Propylheptyl Ether, PEG-7m, PEG-8 Dimethicone / Polysorbate 20 Crosspolymer, PEG-8 Propylheptyl Ether, PEG-9m, PEG-12 Carnauba, PEG-12 Glyceryl Linoleate, PEG-14m, PEG-20m, PEG-23m, PEG-65m, PEG-90m, PEG-100 / IPDI Copolymer, PEG-114 Polylactic Acid, PEG-115m, PEG-1, 60m, PEG-180m, PEG-400, PEG-45 / Dodecyl Glycol Copolymer, PEG-450, PEG-500, PEG / PPG-10 / 3 Oleyl Ether Dimethicone, PEG / PPG-100 / 70 Tocopheryl Ether, Bis-PEG / PPG-15 / 5 Dimethicone, PEG / PPG-18 / 18 Isostearate, PEG / PPG-18 / 18 Laurate, PEG / PPG-2 / 5 Tocopheryl Ether, PEG / PPG-20 / 23 Dimethicone, Bis-PEG / PPG-20 / 5 PEG / PPG-20 / 5 Dimethicone, PEG / PPG-2000 / 200 Copolymer Polymer, peg / ppg-23 / 6 dimethicone, peg / ppg-30 / 10 tocopheryl ether, peg / ppg-5 / 10 tocopheryl ether, peg / ppg-5 / 20 tocopheryl ether, peg / ppg-5 / 30 tocopheryl ether, peg / ppg-50 / 20 tocopheryl ether, peg / ppg-6 / 4 dimethicone, peg / ppg-70 / 30 tocopheryl ether, peg / ppg-8 / 3 laurate, pentadecyl alcohol, petrolatum wax microcrystals, phosphatidic acid, phosphatidylserine ... Diglycerol, Pinemidopropyl Betaine, Poly C10-30 Alkyl Acrylate, Polyacrylate Crosspolymer-4, Polyacrylate Crosspolymer-6, Polyacrylate Crosspolymer-11, Polyacrylate Crosspolymer-14, Polyacrylate-10, Polyacrylate-11, Polyacrylate-27, Polyacrylate-28, Polyacrylic Acid, Polyester-14, Polyester-15, Polyethylene / Isopropyl Maleate / MA Copolyol, Polyglyceryl-2 Diisostearate / Ip Dicopolymer, Hexadecyl Ether, Polyacrylate Crosspolymer-2 ... Helianthus annuus (matricaria) seed oil fatty acids / polyglyceryl-3 citrate crosspolymer, polyglyceryl-4 diisostearate / polyhydroxystearate / sebacate, polyglyceryl-6 behenate, polypropanediol, polypropylene terephthalate, polyquaternium crosspolymer-2, polyquaternium-65, polyquaternium-83, polyquaternium-102, polyquaternium-103, polysilicone-25, polyurethane-29, polyvinyl acetate, polyvinylpyrrolidone, potassium alginate, potassium behenoyl hydrolyzed rice protein,Potassium behenoyl hydroxyproline, potassium carbomer, potassium carrageenan, potassium stearoyl hydrolyzed rice protein, potassium undecylenoyl alginate, potassium undecylenoyl carrageenan, potassium undecylenoyl hydrolyzed corn protein, potassium undecylenoyl hydrolyzed soy protein, potassium undecylenoyl hydrolyzed wheat protein, hydrolyzed potato tuber extract, ppg-4 jojoba alcohol, ppg-4 laureth-2, ppg-4 laureth-5, ppg-6-laureth-3, ppg-20 tocophereth-5, ppg-10 jojoba acid, ppg-2-buta-2, propyl ester of PVM / MA copolymer, Prunus amygdalus dulcis oil unsaponifiables, pseudozyma epicola / camellia sinensis sinensis Seed Oil / Glucose / Glycine Soja Meal / Malt Extract / Yeast Extract Ferment Filtrate, PVP Montmorillonite, PVP / Decene Copolymer, Pyrus Malus Fiber, Quaternium-90 Sepiolite, Rhamnolipids, Sclerotium Gum, Hydrogenated Sesame Seed Oil, Sesquiethoxytriethanolamine, Sesquioctyldodecyl Lauroyl Glutamate, Shea Butter Glycerides, Silica Dimethyl Silylate, Silica Silylate, Beta-Sitosterol, Sodium Acrylates / Sodium Acryloyldimethyl Taurate / Dimethylacrylamide Crosspolymer, Sodium Acrylates / Sodium Acryloyldimethyl Taurate Copolymer, Sodium Acrylates / Sodium Acryloyldimethyl Taurate / Acrylates Mido copolymer, sodium acrylate / vinyl alcohol copolymer, sodium acrylate / vinyl isodecanoate crosspolymer, sodium acryloyldimethyltaurate / acrylamide / VP copolymer, sodium acryloyldimethyltaurate / VP crosspolymer, sodium arachidate, sodium C4-12 olefin / maleic acid copolymer, sodium carbomer, sodium carboxymethylcellulose, sodium carboxymethyl dextran, sodium carboxymethyl starch, sodium carrageenan, sodium cellulose sulfate bound,Sodium Cocoyl Barley Amino Acids, Sodium Cocoyl / Stearoyl(Alanine / Arginine / Asparagine / Aspartic Acid / Glutamic Acid / Glutamine / Glycine / Histidine, Sodium Cyclodextrin Sulfate, Sodium Dextrin Octenyl Succinate, Sodium Lanet Sulfate, Sodium Polyacrylate, Sodium Starch Polyacrylate, Sodium Polyacryloyldimethyltaurate, Sodium Polygamma-Glutamate, Sodium Polygamma-Glutamate Crosspolymer, Sodium Polyglutamate Crosspolymer, Sodium Polymethacrylate, Sodium Polynaphthalene Sulfonate, Sodium Polystyrene Sulfonate, Sodium Starch Octenyl Succinate, Sodium Styrene / MA Copolymer, Sodium Tocopheryl Phosphate Antioxidant, Trehalose Sodium Octenyl Succinate , Sodium alginate, Sodium TEA-undecylenoyl alginate / TEA-undecylenoyl carrageenan, Sorbitan palmitate, Phthalate soy protein, Soybean oil fatty acid amide, Sparassis crispa extract, Starch hydroxypropyltrimonium chloride, Isosteareth-200 palmitate, Stearic acid, Stearyl alcohol, Stearyl glycol, Stearyl vinyl ether / MA copolymer, Stearyl ureth gum, Stigmalyl chloride, Stigmasteryl nonanoate, Stigmasteryl succinate, Styrene / MA copolymer, Sucrose polypalmitate, Sunflower seed oil ethyl ferrate ester, Sunflower seed oil polyglyceryl-10 ester, Sunflower seed oil polyglyceryl-6 ester, Tallow alcohol, Tallow amide cosmetic, Tamarindus seed gum indica seed gum), TEA-Alginate, TEA-Dextrin Octenyl Succinate, Tetradecyl Eicosanoic Acid, Tetradecyl Octadecanoic Acid, Tetradecyl Octadecyl Behenate, Tetradecyl Octadecyl Myristate, Tetradecyl Octadecyl Stearate, Tetrasodium Etidronate, Theobroma Grandiflorum Seed Butter Glyceryl Esters, Tocopheryl Succinate Methylglucamide, Tremella Fusiformis Polysaccharide, Triacontene / VP Copolymer, 1-Tridecanol,Tripropylene glycol, Undeceth-40, Undecylenoyl inulin, Undecylenoyl xanthan gum, Vinyl alcohol / vinyl formamide copolymer, Bis-vinyl dimethicone / dimethicone copolymer, Bis-vinyl dimethicone / PEG-10 dimethicone crosspolymer, Hydrogenated microcrystalline wax, Welan gum, Xanthan gum, Zinc undecylenoyl hydrolyzed wheat protein.,

[0148] In an embodiment, a biopolymer composition or suspension according to the present invention meets the ISO 11930 Preservative Effectiveness Test, a procedure for evaluating the antimicrobial protection of a product. This test was written specifically for cosmetics and is quickly becoming the "mainstream" test method for evaluating the preservative effectiveness of cosmetic and personal care products. In an embodiment, a biopolymer composition or suspension according to the present invention provides cosmetically useful antimicrobial protection against one or more strains of microorganisms, including but not limited to Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Candida albicans, and A. brasiliensis.

[0149] As shown in Example 6, insoluble and / or semi-soluble biopolymers can act as emulsifiers and can act advantageously as emulsifiers for stable emulsions.

[0150] In an embodiment, the biopolymer composition or suspension is obtained by a process other than chemical processing. In an embodiment, the biopolymer composition or suspension according to the present invention is obtained by subjecting the biopolymer and the polar solvent to high shear conditions, e.g., high mechanical energy. In an embodiment, the high shear conditions and / or high mechanical energy are obtained by processes including, but not limited to, mechanical shear, shear thinning, planetary ball milling, rolling mill, vibratory ball mill, tumbling agitation ball mill, horizontal media mill, colloid milling. As shown below, the high shear conditions and / or high mechanical energy can be carried out for a period of time, under parameters, under suitable conditions, etc., until a desired state change is obtained, such as, for example, a color change, a viscosity change, a change from a slurry to a paste, an ointment, a cream, a lotion, a gel, or a milk.

[0151] In embodiments, the high shear conditions and / or high mechanical energy require the use of suitable devices or equipment, including, but not limited to, ball mills (e.g., planetary ball mills, rolling mills, vibratory ball mills, rolling agitator ball mills, horizontal media mills, colloid mills, magnetic mills), twin screw extruders, high pressure homogenizers, blade homogenizers, agitator homogenizers, dispersers, rotor stator homogenizers, high shear mixers, plow share mixers, dynamic mixers, plow mixers, turbine mixers, speed mixers, attrition mirrors, sonicators, tissue tearers, cell lysers, polytrons, ribbon agitators, microfluidizers, and combinations thereof. In a preferred embodiment, the present invention utilizes ball milling under wet conditions.

[0152] The desired properties of the compositions or suspensions according to the invention (e.g., physical and chemical properties, purity, presence or absence of added chemicals, etc.) can be characterized using any suitable method or technique known in the art. Examples include, but are not limited to, scanning electron microscopy (SEM) to characterize particle size, rheology to characterize thixotropy and shear thinning behavior, X-ray diffraction (XRD) to characterize crystallinity, dynamic light scattering (DLS) to characterize particle size distribution, Fourier transform infrared spectroscopy (FTIR) spectroscopy that can be used to obtain infrared absorption, emission, and photoconductivity spectra of solids, liquids, and gases, solid-state nuclear magnetic resonance characterization (SSNMR) that can be used to study amorphous materials, and detect different components present in the composition, atomic force microscopy (AFM), mass spectrometry to characterize wet particle size, cryo-scanning electron microscopy (cryo-SEM) to characterize wet / frozen particle size, liquid color analysis to characterize the color of the sample, etc.

[0153] Process for obtaining biopolymer compositions and suspensions Further aspects of the present invention relate to processes and methods for obtaining the biopolymer compositions and suspensions defined herein.

[0154] According to one particular aspect, the present invention relates to a mechanical process for obtaining a biopolymer composition, comprising subjecting an insoluble and / or semi-soluble biopolymer to mechanical energy in the presence of a polar solvent to obtain a stable homogenous suspension of the insoluble and / or semi-soluble biopolymer.

[0155] Without wishing to be bound by any theory, it is proposed that mechanical energy results in shearing and / or shear thinning of the biopolymer, as shown above. Mechanical energy may also result in a certain "decomposition" or "conversion" of multimeric biopolymers into smaller monomeric units.

[0156] Thus, another particular aspect of the present invention relates to a process for obtaining a biopolymer composition, comprising subjecting insoluble and / or semi-soluble biopolymers to high shear conditions in the presence of a polar solvent until a change in state is observed and a stable homogenous suspension of insoluble and / or semi-soluble biopolymers is obtained.

[0157] In embodiments, the insoluble biopolymer is selected from chitin, chitosan, cellulose, hemicellulose, lignin, amylose, actin, fibrin, collagen, silk, fibroin, keratin, wool, and mixtures thereof. In embodiments, the semi-soluble biopolymer is selected from gelatin, pectin, starch, amylopectin, agarose, alginic acid, alginate, hyaluronic acid, RNA, DNA, xanthan gum, guar gum, carrageenan, latex, polymannan, suberin, cutin, cutan, and mixtures thereof.

[0158] In embodiments, the insoluble or semi-soluble biopolymers are obtained from fungi and mushrooms. In embodiments, the insoluble or semi-soluble biopolymers are obtained from plant materials including, but not limited to, roots, tubers, leaves, petals, seeds, fruits, etc. In certain embodiments, the biopolymer suspension or biopolymer composition according to the present invention is obtained by subjecting plant materials from one or more of the following to high shear conditions and / or high mechanical energy: Pomponella, Asaï, Alder Buckthorn, Alfalfa, Aloe Vera, Amago, Arnica, Asafoetida, Asthma-plant, Ashwagandha, Asthma-plant, Astragalus, Abanum Senna, Balloon Flower, Barberry, Bajra, etc. laurel, bay leaf, belladonna, benjamin, billin glye, bilberry, bitter leaf, bitterwood, black cohosh, milk thistle, crepe grass, blueberry, borage, burdock, calendula, camelina, cannabis, caraway, carrot, cat's claw, cayenne, celery, centella, chamomile, chaparral, charcoal tree, chasteberry, chickweed, chicory, chili, cinchona, cinnamon, clove, clover, cocoa, coffee senna, comfrey, coriander, coco sunflower, cranberry, cucumber, cumin, daisy, dandelion, doodah, foxglove, dock, dogwood, angelica, drumstick tree, echinacea, elderberry, elderflower, elecampe, ephedra, eucalyptus, eyebright, sonchus poppy, fenugreek, moonflower, feverfew, knautia arvensis, linseed, foxglove, fumithry, galanga, ganja, garden angelica, garlic, geranium, ginger, ginkgo, ginseng , goldenseal, gotu kola, grape, kakidoushi, guava, acacia, willow, hawthorn, heena, helichrysum, hemp, henna, hepatica, hibiscus, hollyhock, hoodia, horse chestnut, horsetail, hops, hyssop, inch plant, jasmine, kalonji, canna, capricacil, kalvi, kava, khat, konjac, kratom, lady's mantle, laurcinus, lavender, lemon, lemon balm, lemon citrus, lycan, licorice, lily, licorice, lotus, langoustine,madreselva, magnolia bark, mallow, manjistha, marigold, marijuana, marshmallow, melon, milk thistle, mintroot, mint, mistletoe, moringa, mullein, myrrh, neem, nettle, nigella, noni, oat, opium poppy poppy, orange, oregano, orris, pansy, papaya, passion flower, peppermint, plantai, plantain, bellflower, poppy, primrose, purple coneflower, Robert geranium, rose, rosemary, saffron, sage, sarae, sandalwood, saponaria, savory, sea buckthorn, deer laurel, purslane, small-leaved linden, snapdragon root, snowdrop, soapwort, speedwell, St. John's wort, star anise, summer snowflake , sunflower, calamus, peganum harmala, tea, tea tree oil, thyme, tomato, tulsi, turmeric, umaca, valerian, velvet leaf, verbena, veronica, vetiver, violet, hops, purple juniper, water germander, water plantain, water cress, wheat germ, wheatgrass, white buttercup, Japanese laurel, willow bark, cherry, witch hazel, yarrow, lady's slipper, yarbamate, yarba santa, and zedoaria.

[0159] In embodiments, the polar solvent is selected from polar protic solvents, polar aprotic solvents, and mixtures thereof. The polar solvent may be an aqueous solvent. The present invention encompasses the use of two or more solvents of the same or different categories. Contemplated examples of polar protic solvents, polar aprotic solvents, and aqueous solvents are as defined above.

[0160] Various biopolymer sources can be used, and the present invention is not limited to a specific source of material.For example, suitable sources of chitin can include, but are not limited to, green plants, algae and fungi.Suitable sources of chitin and chitosan can include, but are not limited to, fungi, crustaceans (e.g., crabs and shrimp) and insects.

[0161] In embodiments, the biopolymer subjected to mechanical energy or high shear conditions is a powder of pure biopolymer material (e.g., Sigma). In embodiments, the biopolymer is a dry biopolymer (e.g., not wetted and / or not swollen). In embodiments, the biopolymer is a dry biopolymer that is not a dried wet biopolymer (such wet-and-dried biopolymers typically appear porous in SEM).

[0162] In embodiments, the biopolymer is a biopolymer other than wet chitin, pre-wet chitin and / or swollen chitin, such as chitin extracted from a shell and exposed to acid for demineralization and base for deproteinization. In embodiments, the biopolymer is a biopolymer that is initially in a dry form and then wet, pre-wet and / or swollen before being subjected to mechanical energy / high shear conditions.

[0163] According to the invention, it may also be envisaged to use "less pure" extracts of biopolymers such as extracts obtained from prawn shells, crab shells, shrimp shells, lobster shells, insects, fungi, wood, plant cellulose, etc.

[0164] In an embodiment, the biopolymer composition or suspension is achieved without the use of catalysts or other chemical additives. In an embodiment, the process of the present invention does not require chemical processing, which is different from existing methods that typically require chemical residues such as acids, bases, reactive chemicals, and / or organic and / or inorganic salts for production. Thus, the process of the present invention can provide biopolymer compositions and suspensions that are substantially free of any chemicals, additives, etc., as defined above. Avoiding chemicals is advantageous for obtaining biopolymer compositions and suspensions that are substantially pure, natural, biocompatible, biodegradable, and / or free of toxic components.

[0165] In embodiments, the high shear conditions and / or high mechanical energy are obtained by processes including, but not limited to, mechanical shearing, shear thinning, planetary ball milling, rolling, vibratory ball milling, tumbling agitator ball milling, horizontal media milling, colloid milling.

[0166] Whenever necessary or preferred, the biopolymer material used in the suspension process may be modified prior to being subjected to mechanical energy or high shear conditions. Examples of possible modifications include, but are not limited to, shearing, grinding with blade grinders, freeze-thawing, and / or dry ball milling to reduce particle size.

[0167] In embodiments, the high shear conditions and / or high mechanical energy require the use of suitable devices or equipment, including, but not limited to, ball mills (e.g., planetary ball mills, rolling mills, vibratory ball mills, tumbling agitator ball mills, horizontal media mills, colloid mills), twin screw extruders, high pressure homogenizers, blade homogenizers, agitator homogenizers, dispersers, rotor stator homogenizers, high shear mixers, plow share mixers, dynamic mixers, plow mixers, turbine mixers, sonicators, tissue tearers, cell lysers, polytrons, ribbon agitators, microfluidizers, and combinations thereof.

[0168] In one particular embodiment, the process is carried out using a vertical planetary mill (e.g., Tencan XQM-2A™) with a 100 mL capacity zirconia jar and 10 mm diameter zirconia balls. Other types of balls (e.g., 5 mm to 15 mm) and other jar sizes (i.e., 250 mL) can also be used. In one particular embodiment, the process is carried out using a Flacktek™ Speedmixer (DAC 330-11 SE) equipped with a 40 mL zirconia jar with 5 mm diameter zirconia balls or zirconia rings. In one particular embodiment, the process is carried out using a 1.5 L Supermill Plus™ using 1.4 to 1.7 mm zirconia beads.

[0169] The invention encompasses various methods of using a ball mill, including, but not limited to, unidirectional milling continuously (no pauses), unidirectional milling with periodic pauses (e.g., at either 10, 20, or 30 minutes), alternating milling directions with periodic pauses (e.g., at either 10, 20, or 30 minutes), etc. In embodiments, the method involves milling the biopolymer for a period of time (e.g., 10 minutes, 15 minutes, or 20 minutes, or 30 minutes or more), followed by a short pause (e.g., 30 seconds, or 1 minute, or 2 minutes, or 5 minutes, or 10 minutes, or 15 minutes or more), and then milling in the opposite direction for a period of time (e.g., 10 minutes, 15 minutes, or 20 minutes, or 30 minutes or more), for a total of 1 hour, or 2 hours, or 3 hours, or 5 hours, or 10 hours, or 12 hours, or 15 hours, or more of alternating milling.

[0170] In certain embodiments, biopolymer compositions and suspensions according to the invention are obtained using a specific protocol, referred to herein as the "10+1 alternative method". This method involves grinding the biopolymer for a period of time (e.g., 10 minutes), followed by a short pause (e.g., 1 minute), and then grinding in the opposite direction for a period of time (e.g., 10 minutes), for a total of 1 hour, or 2 hours, or 3 hours, or 5 hours, 10 hours, or 12 hours. The use of the method is described in Examples 8 to 27.

[0171] Advantageously, the viscosity of the composition / suspension can be modified by varying the high shear conditions and / or mechanical energy to which the biopolymer is subjected. These conditions can be adjusted to obtain a stable homogeneous suspension with a desired viscosity (e.g., a stable colloidal homogeneous suspension). For example, as shown in Figure 1, the viscosity can be altered such that the biopolymer composition or suspension becomes a paste, ointment, cream, lotion, gel or milk with a reduced viscosity. Typically, providing more mechanical energy increases the shear and correspondingly reduces the viscosity of the final product.

[0172] Exemplary conditions or parameters that can be varied include, but are not limited to, speed (e.g., revolutions per minute (RPM)), vessel size, ball quantity, ball size, vessel media, ball media, processing time, processing cycle, and batch size, ratio of components (e.g., biopolymer:solvent weight ratio), and the like.

[0173] In embodiments, the biopolymer and the aqueous solvent have a weight ratio of biopolymer:solvent of about 0.2:20 to about 10:20, or about 0.5:20 to about 3:20, or about 0.75:20, or about 1.0:20, 1.25:20, or about 1.5:20.

[0174] In embodiments, the mechanical energy or high shear conditions are performed until a color change is observed. In embodiments, such color change includes a change from a clear solution with powder deposits to an opaque off-white homogeneous suspension with the viscosity of a thick paste (see FIG. 1 and Table 1). In one particular embodiment, the method includes providing a specific mechanical energy of at least 0.4 to 500 W / kg relative to the total amount of material of the system (i.e., biopolymer+solvent+additives).

[0175] In embodiments, the mechanical energy or high shear conditions are carried out for at least 15 minutes, or at least 30 minutes, or at least 45 minutes, or at least 60 minutes, or at least 90 minutes, or at least 2 hours, or at least 3 hours, or at least 5 hours. In embodiments, the mechanical energy / high shear conditions are carried out for a period and duration that results in the "decomposition" of the polymeric biopolymer into smaller monomeric units. In embodiments, the polymeric biopolymer is a polysaccharide and the monomeric unit is a monosaccharide. For example, the polymeric biopolymer can be chitin, and the monomeric unit can be N-acetylglucosamine (GlcNAc).

[0176] Table 1 below provides non-limiting examples of desirable viscosities of compositions / suspensions according to the present invention.

[0177] Table 1: Examples of desired viscosities [Table 1]

[0178] As demonstrated in the examples, the process of the invention can also be used to prepare stable emulsions containing oils and / or waxes (Examples 6, 18 and 24), or containing N-acetylglucosamine (Example 16), or containing the following additives added to a cellulose suspension: cetyl alcohol, glyceryl stearate, soy butter, PC90, tara gum, PSC3, PEG, guar, xanthan gum, agarose, sodium hyaluronate, Tween 80™ and glycerin (Example 20), with emulsifiers and preservatives (Example 27). Subjecting any of these compounds to mechanical energy or high shear conditions in the presence of insoluble and / or semi-soluble biopolymers as defined herein can result in stable emulsions.

[0179] The process of the present invention may further include additional steps including one or more pretreatment steps including, but not limited to, pre-grinding, microwave treatment, freeze-thawing and steam treatment. In one particular embodiment, the process includes pre-grinding the biopolymer in a dry environment to reduce a certain size and / or to obtain a fine powder (e.g., less than about 10 μm, or less than 5 μm, or less than 3 μm). In an embodiment, the pre-grinding is carried out for at least 15 minutes, or at least 30 minutes, or at least 45 minutes, or at least 60 minutes, or at least 90 minutes, or at least 2 hours, or at least 3 hours, or at least 5 hours, or at least 9 hours, or at least 12 hours. In another particular embodiment, the method includes a pre-treatment step of freezing / thawing the biopolymer material in water (e.g., 1, 2, 3 or more freeze-thaw cycles) before a high shear step such as grinding. In another particular embodiment, the method includes a pre-treatment step of microwave treatment and / or steam treatment of the biopolymer material before a high shear step such as grinding. In another particular embodiment, the method includes a pretreatment step of pre-grinding the biopolymer material with propanol (eg, isopropanol) prior to a high shear step such as milling.

[0180] In embodiments, the process of the present invention does not include and / or does not explicitly exclude steps or techniques that may have been used in existing prior art methods for obtaining biopolymer compositions or suspensions, including, but not limited to, precipitation, centrifugation, filtration, sonication, homogenization (e.g., high pressure homogenizers), freeze-drying, salification, grinding, stamping, swelling, mashing, cryogenic grinding (e.g., liquid nitrogen in combination with an agitating ball mill), stirring, mixing and / or high shear with an impeller, microfluidization, embrittlement, and attrition milling.

[0181] The process of the present invention may further comprise adding one or more additives as defined herein before, during and / or after the pretreatment step and / or before, during and / or after the high shear and / or high mechanical energy step.

[0182] It is within the knowledge of one skilled in the art to scale up the production of the compositions and / or formulations of the present invention according to specific needs (e.g., to obtain at least 1.5 liters, or at least 15 liters, or at least 45 liters, or at least 75 liters, or at least 100 liters, or at least 150 liters or more). For example, existing equipment for obtaining higher volume and high shear conditions includes, but is not limited to, SuperMill Plus Media Mill™ 1.5 liter, SuperMill Plus Media Mill™ 15 liter, SuperMill Plus Media Mill™ 45 liter, Batch Mill™ Model 100, Batch Mill™ Model 256, Double Planetary™ Mixer, Planetary Plus™ Mixer 7 liter, Planetary Plus™ Mixer 150 liter, Ram Press, Three Roll Mill, and SHRED / In-line Rotor Stator.

[0183] [Commercial use] The compositions and formulations of the present invention may find numerous uses.

[0184] Another aspect of the present invention relates to a cosmetic composition comprising a biopolymer composition or suspension as defined herein. In an embodiment, the cosmetic composition is formulated as a paste, ointment, cream, lotion, gel or milk. In an embodiment, the cosmetic composition is formulated as a skin care composition, hair care composition, base composition, vehicle composition, anti-aging composition, sunscreen blocking composition, moisturizing composition, make-up composition. Advantageously, the cosmetic composition may comprise smaller monomer units of multimeric biopolymers such as oligomers of acetylglucosamine (GlcNAc) and / or NAG, thus exhibiting anti-aging and / or UV blocking properties.

[0185] The compositions and formulations of the present invention can find many applications in various fields, and are not limited to cosmetic applications.For example, it can be envisaged that the compositions and formulations defined herein can be used as seed coatings, surgical implant coatings, food additives, paints, material additives, drug release platforms, etc.

[0186] Those skilled in the art will recognize or be able to ascertain, using no more than routine experimentation, numerous equivalents to the specific procedures, embodiments, claims, and examples described herein. Such equivalents are considered to be within the scope of the present invention and are included in the appended claims. The present invention is further illustrated by the following examples, which should not be construed as further or specifically limiting. EXAMPLES

[0187] This section presents non-limiting examples for obtaining stable homogenous suspensions of biopolymers according to the present invention. Unless otherwise stated, the shearing process is carried out using a vertical planetary mill (i.e., Tencan XQM-2A™) with 100 mL capacity zirconia jars and 10 mm diameter zirconia balls. Other types of balls (i.e., 5 mm to 15 mm) and other jar sizes (i.e., 250 mL) have also been used successfully.

[0188] [Example 1: Grinding of chitin and water (ratio 0.75:20)] Chitin was soaked in water and ground at a ratio of 0.75:20 w / w (chitin:water) using 15 balls of 10 mm diameter at 670 RPM for 3 hours.

[0189] This produced isolated fibers with nano-sized widths at a low shear rate viscosity of 11819 mPaS, as shown in Figures 6, 7, 8 and 9. SEM images show partial fibrillation of the chitin fibers, in which aggregation is present, represented by globular as well as various sized fibers, and amorphous regions persist compared to the more uniform crystalline rods of nanochitin in acid-treated chitin.

[0190] [Example 2: Grinding of chitin and water (ratio 1.5:20)] Chitin was soaked in water and ground with 30 balls of 10 mm diameter at 670 RPM for 3 hours in a ratio of 1.5:20 w / w (chitin:water). Chitin was pre-ground with 30 balls at 670 RPM for 3 hours.

[0191] As shown in Figures 4, 5, 10 and 11, this produced isolated fibers with nano-sized widths at a low shear rate viscosity of 6105 mPaS. This indicates that pretreatment can significantly reduce the viscosity of the suspension when compared to the dynamic modulus above. Figures 4 and 5 show the spherical aggregates of chitin fibers upon drying for SEM preparation.

[0192] [Example 3: Samples A to F] Various types of samples were prepared to verify the robustness of the present invention under different conditions, and each sample was measured in triplicate.

[0193] Briefly, samples were labeled A-F and prepared as described below. Capital letters indicate how the suspension was prepared before and after it was prepared for SEM scanning. Capital letters indicate one of the following: diluted, labeled with a letter (e.g., A); further diluted and sonicated, labeled with a letter and number 1 (e.g., A1), or lyophilized (FD), labeled with a letter and number 1 along with FD (e.g., A1+FD).

[0194] Sample A: Chitin milled with water in a ratio of 0.75:20 using 15 balls at 670 RPM for 3 hours. This sample corresponds to Example 1 defined above.

[0195] Sample B: Chitin milled with water in a ratio of 1.00:20 using 30 balls at 670 RPM for 9 hours.

[0196] Sample C: Dry chitin milled with 5 balls at 670 RPM for 15 minutes. Chitin milled with 30 balls at 670 RPM for 3 hours with water in a 1.00:20 ratio.

[0197] Sample D: Dry chitin milled with 5 balls at 670 RPM for 1 hour. Chitin milled with 30 balls at 670 RPM with water in a ratio of 1.00:20 for 3 hours.

[0198] Sample E: Dry chitin milled with 30 balls at 670 RPM for 3 hours. Chitin milled with 30 balls at 670 RPM with water in a ratio of 1.25:20 for 3 hours.

[0199] Sample F: Dry chitin milled with 30 balls at 670 RPM for 3 hours. Chitin milled with 30 balls in a 1.50:20 ratio with water at 670 RPM for 3 hours. This sample corresponds to Example 2 defined above.

[0200] The results are shown in Figures 2 and 3. In particular, in chitin suspensions, particles varied from 50 nm to 9 µm, with average sizes ranging from 200 nm to 3 µm (Figure 2). Fiber widths, as aggregates, varied from 7 nm to 3 µm, with averages ranging from 20 nm to 93 nm (Figure 3A). Fiber lengths in these samples ranged from 350 nm to 2.5 µm (Figure 3B).

[0201] Table 2 below shows the measured viscosities for Samples A-F. Table 2: Measured viscosities of samples A-F [Table 2]

[0202] The results of these experiments show that pre-milling reduces the viscosity of the final suspension. Viscosity also decreased as the number of balls increased and the mill time and speed (i.e., RPM) increased.

[0203] On the other hand, it was also possible to obtain suspensions with high viscosity. In one experiment, chitin was milled with 10 balls at 670 RPM for 3 h in a ratio of 1.00:20 with water, giving a viscosity of 40,028 mPa·s (data not shown). In another experiment, chitin was milled with 20 balls at 670 RPM for 3 h in a ratio of 1.50:20 with water, giving a viscosity of 85,608 mPa·s (data not shown).

[0204] Milling strongly affected the powder X-ray diffraction (pXRD) pattern. Figure 3C shows the powder X-ray diffraction of commercial chitin before milling. The X-ray pattern demonstrates that it is chitin based on the peak positions at approximately 9.5° and 19.5° 2θ. Therefore, this pattern was considered to correspond to the signature of chitin by the present technique (i.e., the benchmark).

[0205] The X-ray patterns of Samples 3A-F in suspension (not dried) are shown in Figures 3D-I. Overall, the patterns show that the sample is partially crystalline and partially amorphous, but the X-ray pattern demonstrates that it is chitin based on the peak positions at approximately 9.5° and 19.5° 2θ.

[0206] Example 4: Further biopolymer suspensions To demonstrate that the invention is applicable to many different biopolymers, the following insoluble biopolymers were used in the process according to the invention: chitin, chitosan, cellulose (fibrous, alpha, microcrystalline), collagen (bovine) and silk.

[0207] Briefly, the biopolymers were ground in water with ten 10 mm diameter balls at a ratio of 1:20 at 670 RPM for 3 hours. Stable homogenous suspensions were successfully obtained for all these biopolymers, as shown in Figures 12A-17B.

[0208] Similarly, silk was pre-milled with 40 balls of 10 mm diameter for 3 hours and dried. Silk fibroin was milled with 40 balls in a 1:20 ratio with water at 670 RPM for 1 hour. The biopolymer was used to obtain a stable homogenous suspension, as shown in Figures 18A and 18B.

[0209] Example 5: Combination of biopolymers Chitin and chitosan were milled in water with 30 10 mm diameter balls in a ratio of 0.5:0.5:20 (chitin:chitosan:water) at 670 RPM for 3 hours, resulting in a stable homogenous suspension (see Figure 19A).

[0210] Chitin and chitosan were milled in water with 30 10 mm diameter balls in a ratio of 0.6:0.4:20 (chitin:chitosan:water) at 670 RPM for 3 hours, resulting in a stable homogenous suspension (see Figure 19B).

[0211] [Example 6: Additives] Chitin and beeswax Chitin and beeswax were milled in water with 50 10 mm diameter balls in the ratio 1:0.25:20 (chitin:beeswax:water) at 670 RPM for 3 hours. A stable homogenous suspension was obtained (see Figure 20).

[0212] Chitin and vegetable oil Chitin and vegetable oil were milled in water with 30 10 mm diameter balls in a ratio of 1:20:20 (chitin:vegetable oil:water) at 670 RPM for 3 hours. A stable homogenous suspension was obtained (see Figure 21A).

[0213] Chitin and vegetable oil were milled in water with 30 10 mm diameter balls in a ratio of 1:2:20 (chitin:vegetable oil:water) at 670 RPM for 3 hours. A stable homogenous suspension was obtained (see FIG. 21B).

[0214] Chitin and vegetable oil were milled in water with 30 10 mm diameter balls in a ratio of 1:1:20 (chitin:vegetable oil:water) at 670 RPM for 3 hours. A stable homogenous suspension was obtained (see FIG. 21C).

[0215] Chitin and soybean oil Chitin and soybean oil were milled in water with 30 10 mm diameter balls in a ratio of 1:20:20 (chitin:soybean oil:water) at 670 RPM for 3 hours. A stable homogenous suspension was obtained (see Figure 22).

[0216] Example 7: Mixing of solvents A combination of two solvents, glycerin + water, was tested. Briefly, chitin and glycerin were milled in water with 50 10 mm diameter balls in the ratio 1:0.5:20 (chitin:glycerin:water) at 670 RPM for 3 hours. A stable homogenous suspension was obtained (Figure 23).

[0217] Example 8: Characterization of samples by FTIR, SSNMR, and PXRD 1) Sample preparation

[0218] The following samples were prepared and used for characterization by FTIR, SSNMR, and PXRD: Milling is carried out using a vertical planetary mill (Tencan XQM-2A™) with a 100 mL capacity zirconia bottle and 10 mm diameter zirconia balls.

[0219] silk

[0220] The fluffy silk was pre-ground and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute break, then ground in the opposite direction for 10 minutes, for a total of 3 hours.

[0221] A silk suspension was produced by grinding the pre-ground silk in water in a ratio of 2.00:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then ground in the opposite direction for 10 minutes, for a total of 1 hour.

[0222] cellulose

[0223] The cellulose suspension was produced by milling cellulose in water in a ratio of 1.50:20 using 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 1 hour.

[0224] collagen

[0225] The collagen was pre-milled and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 2 hours.

[0226] The collagen suspension was produced by milling pre-milled collagen in water in a ratio of 2.00:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 6 hours.

[0227] Alginate

[0228] The alginate suspension was produced by milling alginate in water at a ratio of 20 with 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0229] Chitin

[0230] A chitin suspension was produced by grinding chitin in water in a ratio of 1.00:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0231] Chitosan

[0232] The chitosan was pre-milled and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute break and then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0233] A chitosan suspension was produced by milling pre-milled chitosan in water in a ratio of 0.75:20 with 30 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0234] 2) Fourier transform infrared spectroscopy (FTIR) analysis

[0235] The polymer suspension was prepared as described above. The suspension was then dried and ground into a powder for FTIR spectroscopy. A total of 24 cumulative scans were acquired in the range of 4000 cm-1 to 400 cm-1 at a resolution of 4 cm-1. The graphs of the FTIR spectroscopy are shown in Figures 24A-24F.

[0236] silk

[0237] A graph of the FTIR spectroscopy analysis of this sample is shown in Figure 24 A. Relevant peaks are 3600-2800 cm-1 -OH and NH stretches, 1630, 1509, and 1222 cm-1 amide.

[0238] cellulose

[0239] The FTIR spectroscopy graph of this sample is shown in Figure 24B. Relevant peaks are 3300 cm-1-OH stretch, 1624 cm-1-water molecule absorbed in cellulose, ~1348 cm-1-CH2 and CH3 bend, 1011 cm-1-C-O stretch.

[0240] collagen

[0241] The FTIR spectroscopy graph of this sample is shown in Figure 24C. Relevant peaks are 3262 cm-1-NH stretch, 3039, 2917, 2850 cm-1-C-H stretch, 1625, 1523 cm-1-amide bend.

[0242] Alginate

[0243] The FTIR spectroscopy graph for this sample is shown in Figure 24D. Relevant peaks are 3335 cm-1-OH stretch, 2909 cm-1-C-H stretch, 1711, 1617 cm-1-carboxylic acid, 1026 cm-1-C-O stretch.

[0244] Chitin

[0245] The FTIR spectroscopy graph for this sample is shown in Figure 24E. Relevant peaks are: 3245 cm-1-OH stretch, 3070 cm-1-NH stretch, 2903, 2854 cm-1-alkene, 1625, 1540 cm-1-amide, 1022 cm-1-C-O stretch.

[0246] Chitosan

[0247] The FTIR spectroscopy graph for this sample is shown in Figure 24F. Relevant peaks are 3300 cm-1-OH and NH stretches, 2860 cm-1-alkene, 1636, 1546 cm-1-amide, 1020 cm-1-C-O stretch.

[0248] 3) Solid-state nuclear magnetic resonance characterization (SSNMR)

[0249] Solid-state nuclear magnetic resonance (13C) (SSNMR) was used to determine the composition of the biopolymer suspension after drying. The suspension was prepared as described above, then dried and ground into a powder.

[0250] Data were obtained on a 4 mm Varian Chemagnetics™ dual resonance probe. 1 H is 399.9MHz, 13 C were acquired using a VNMRS 400™ broadband spectrometer operating at 100.5 MHz. Recycle delay was 4 seconds. Samples were spun at 13 kHz with a CP contact time of 2 ms and 2048 scans were collected for each sample. Graphs of these analyses are shown in Figures 25A-F.

[0251] silk

[0252] The graph of the SSNMR analysis of this sample is shown in Figure 25 A. The following peak shifts indicate the corresponding functional groups associated with the carbons: 172 ppm-amide; 156 ppm-carbonyl; 62 ppm-C-O; 55 ppm-CH; 49 ppm-CH2; 43 ppm-CH2; 17 ppm-CH3.

[0253] cellulose

[0254] The graph of the SSNMR analysis of this sample is shown in Figure 25B. The following peak shifts indicate the corresponding functional groups associated with carbon: 104 ppm-C-O; 82 ppm-O-CH; 75.4 ppm-O-CH; 62.5 ppm-O-CH2.

[0255] collagen

[0256] The graph of the SSNMR analysis of this sample is shown in Figure 25C. The following peak shifts indicate the corresponding functional groups associated with carbon: 174 ppm-carbonyl / amide; 71 ppm-C-O; 59 ppm to 20 ppm-CH variation; 17 ppm-CH3.

[0257] Alginate

[0258] A graph of the SSNMR analysis of this sample is shown in Figure 25D. The following peak shifts indicate the corresponding functional groups associated with carbon: 170 ppm - carbonyl; 103 ppm - C-O; 79 ppm - O-CH; 72 ppm to 67 ppm - O-CH.

[0259] Chitin

[0260] A graph of the SSNMR analysis of this sample is shown in Figure 25E. The following peak shifts indicate the corresponding functional groups associated with carbon: 174 ppm-carbonyl; 104 ppm-C-O; 83 ppm-55 ppm-O-CH; 23 ppm-CH3.

[0261] Chitosan

[0262] A graph of the SSNMR analysis of this sample is shown in Figure 25F. The following peak shifts indicate the corresponding functional groups associated with carbon: 174 ppm-carbonyl; 104 ppm-C-O; 83 ppm-55 ppm-O-CH; 23 ppm-CH3.

[0263] 4) Power X-ray diffraction (PXRD) characterization

[0264] Power X-ray diffraction (PXRD) was used to investigate the crystallinity patterns of the biopolymer suspensions after drying. Such patterns can be used as a means of identification of the dried products.

[0265] A suspension was prepared as above, then dried and ground into a powder. Sample diffractograms were recorded from 4° to 50° in 0.02 degree increments on a zero background plate using a Bruker D8 ADVANCE™ X-ray diffractometer equipped with a Cu-Kα (λ=1.54 Å) source. PXRD pattern graphs are shown in Figures 26A-26F.

[0266] silk

[0267] A graph of the PXRD pattern of this sample is shown in Figure 26A, with major peaks at 2θ = 10.71°, 20.64°, and 30.45°.

[0268] cellulose

[0269] A graph of the PXRD pattern of this sample is shown in Figure 26B, with major peaks at 2θ = 20.39°, 28.34°, 30.43°, 31.53°, and 35.32°.

[0270] collagen

[0271] A graph of the PXRD pattern of this sample is shown in Figure 26C, with major peaks at 2θ = 8.21°, 19.8°, 20.5°, 26.82°, 28.56°, 30.47°, 31.57°, and 35.48°.

[0272] Alginate

[0273] A graph of the PXRD pattern of this sample is shown in Figure 26D, with major peaks at 2θ = 14.58°, 15.85°, 20.97°, 28.5°, and 30.43°.

[0274] Chitin

[0275] A graph of the PXRD pattern of this sample is shown in Figure 26E, with major peaks at 2θ = 9.58°, 13.06°, 19.62°, 20.95°, 20.62°, 26.40°, 28.36°, 30.43°, 31.57°, and 35.30°.

[0276] Chitosan

[0277] A graph of the PXRD pattern for this sample is shown in Figure 26F, with major peaks at 2θ = 13.52°, 20.21°, 28.42°, 30.33°, 31.63°, and 35.40°.

[0278] Example 9: Characterization of samples by dynamic light scattering (DLS) Dynamic light scattering was used to determine particle size in the suspension. The suspension was prepared as described below.

[0279] 1) Sample preparation

[0280] silk

[0281] The fluffy silk was pre-milled and dried using a 10+1 alternation method with 50 units of 10 mm balls at 670 RPM, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0282] A silk suspension was produced by grinding the pre-ground silk in water in a ratio of 2.00:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then ground in the opposite direction for 10 minutes, for a total of 1 hour.

[0283] cellulose

[0284] A cellulose suspension was produced by milling cellulose in water in a ratio of 1.50:20 using 50 units of 10mm balls at 670RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0285] collagen

[0286] The collagen was pre-milled and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0287] A collagen suspension was produced by milling pre-milled collagen in water in a ratio of 1.25:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0288] Alginate

[0289] An alginate suspension was produced by grinding alginate in water in a ratio of 1.00:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, whereby it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0290] Chitosan

[0291] The chitosan was pre-milled and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute break and then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0292] A chitosan suspension was produced by milling pre-milled chitosan in water in a ratio of 1.50:20 with 30 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 2 hours.

[0293] 2) DLS Measurement

[0294] The samples prepared as above were diluted with water using one drop of sample per 15 mL of water where the dilution was not cloudy. Measurements were completed three times over a period of 2 minutes each time. The temperature was maintained at 25°C, viscosity (cP): 0.8900, refractive index: 1.3310, scattering angle 90°.

[0295] The values ​​determined using DLS represent the swollen polymer particles compared to the dry polymer particles using SEM.

[0296] 3) Results

[0297] Table 3 below summarizes the particle size measurements for each sample.

[0298] Table 3: DLS measurements of the prepared suspensions [Table 3]

[0299] Example 10: Characterization of samples by light transmittance Transmittance demonstrates the ability of light to pass through a material. This measure can indicate the opacity of a suspension and allows spectra to be compared to distinguish between various nanobiopolymer suspensions / solutions.

[0300] 1) Sample preparation

[0301] silk

[0302] The fluffy silk was pre-milled and dried using a 10+1 alternation method with 50 units of 10 mm balls at 670 RPM, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 1 hour.

[0303] The silk suspension was produced by grinding the pre-ground silk in water in a ratio of 1.50:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then ground in the opposite direction for 10 minutes, for a total of 1 hour.

[0304] cellulose

[0305] A cellulose suspension was produced by milling cellulose in water in a ratio of 2.00:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute rest and then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0306] collagen

[0307] The collagen was pre-milled and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 2 hours.

[0308] A collagen suspension was produced by milling pre-milled collagen in water at a ratio of 1.00:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0309] Alginate

[0310] An alginate suspension was produced by grinding alginate in water in a ratio of 1.00:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, whereby it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0311] Chitin

[0312] A chitin suspension was produced by grinding chitin in water in a ratio of 0.60:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, in which it was ground for 10 minutes, followed by a 1 minute rest and then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0313] Chitosan

[0314] The chitosan was pre-milled and dried using a 10+1 alternating method with 30 units of 10 mm balls at 670 RPM where it was milled for 10 minutes followed by a 1 minute rest and then milled in the opposite direction for 10 minutes for a total of 1 hour.

[0315] A chitosan suspension was produced by milling pre-milled chitosan in water in a ratio of 1.00:20 with 30 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 1 hour.

[0316] 2) Measurement of transmittance

[0317] The above samples were measured neat in a quartz cuvette in the Thermo Scientific Evolution™ 260 Bio in % transmittance mode from 200 nm to 800 nm. Furthermore, the absorbance in the range of 400 to 320 nm is the UV-A range and the absorbance in the range of 320 to 280 nm is the UV-B range of the sunscreen. The entire suspension shows an absorbance from 290 nm to 800 nm.

[0318] Graphs of transmittance spectra are shown in Figures 27A-F for silk (Figure 27A), cellulose (Figure 27B), collagen (Figure 27C), alginate (Figure 27D), chitin (Figure 27E), and chitosan (Figure 27F). Although not shown, dilution of the samples increased the percentage of transmittance.

[0319] Example 11: Characterization of samples by scanning electron microscopy (SEM) 1) Sample preparation

[0320] silk

[0321] The fluffy silk was pre-milled and dried using a 10+1 alternation method with 50 units of 10 mm balls at 670 RPM, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0322] The silk suspension was produced by grinding the pre-ground silk in water in a ratio of 1.00:20 with 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, whereby it was ground for 10 minutes, followed by a 1 minute rest, then ground in the opposite direction for 10 minutes, for a total of 15 minutes or 1 hour or 3 hours of grinding.

[0323] cellulose

[0324] The cellulose suspension was produced by grinding cellulose in water in a ratio of 1.00:20 using 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 15 minutes, 1 hour, or 3 hours.

[0325] Alginate

[0326] An alginate suspension was produced by grinding alginate in water in a ratio of 1.00:20 with 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, whereby it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 15 minutes, 1 hour, or 3 hours.

[0327] Chitin

[0328] Chitin suspensions were produced by grinding chitin in water in a ratio of 1.00:20 using 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, in which it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 15 minutes, 1 hour, or 3 hours.

[0329] Chitosan

[0330] The chitosan was pre-milled and dried using a 10+1 alternation method with 30 units of 10 mm balls at 670 RPM where it was milled for 10 minutes followed by a 1 minute stop and then milled in the opposite direction for 10 minutes for a total of 3 hours.

[0331] Chitosan suspensions were produced by pre-milling chitosan in water in a ratio of 1.00:20 using 50 units of 10mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 15 minutes, 1 hour, or 3 hours.

[0332] 2) SEM imaging

[0333] The polymer suspension was prepared as described above. The sample suspension was then diluted dropwise into 5 mL of water. A drop of the diluted solution was added to an SEM stub, which was then coated with platinum prior to measurement.

[0334] SEM pictures are shown in Figures 28A-32G. Table 4 below summarizes the observed properties of samples milled in water for 15 minutes, 1 hour, or 3 hours.

[0335] Table 4: Characteristics of samples evaluated by SEM [Table 4]

[0336] Example 12: Biopolymer Sweep Suspension Test To further investigate the biopolymer / material suspensions produced by milling, sweeps of milled samples and their unmilled versions were compared for visual confirmation of differentiation. Chitin, chitosan, cellulose, collagen, pectin, gelatin and beeswax were tested for suspending ability.

[0337] The finely powdered biopolymer sample was added to water in a ratio of 1:20. The mixture was milled according to a 10+1 alternative method, in which it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0338] Visual assessments before and after milling were evaluated and compared. Chitin, chitosan, cellulose, collagen, and alginate were all found to be insoluble in water before the milling process, but were successfully suspended after milling. However, pectin, gelatin, lignin, guar gum, and xanthan gum showed some or complete dissolution and, in some cases, could be milled to further dissolve. Beeswax is neither dissolved nor suspended by milling; it floats on the surface of the water. Agarose does not dissolve in water and milling produces a thick solid gel. These observations are summarized in Table 5.

[0339] Table 5: Suspension of biopolymers before and after grinding [Table 5]

[0340] Example 13: Rheological behavior Rheological data of biopolymer suspensions can be useful to demonstrate that shear thinning is observed. This can also give examples of the viscosities achieved in specific formulations. Thus, the rheological behavior of various polymer suspensions of chitin, chitosan, cellulose, collagen, silk and alginate, as well as blends consisting of chitin-silk-collagen, chitin-mineral oil, and chitin-beeswax, were investigated.

[0341] 1) Sample preparation

[0342] silk

[0343] The fluffy silk was pre-milled and dried using a 10+1 alternation method with 50 units of 10 mm balls at 670 RPM, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 6 hours.

[0344] The silk suspension was produced by grinding the pre-ground silk in water in a ratio of 2.00:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then ground in the opposite direction for 10 minutes, for a total of 6 hours.

[0345] cellulose

[0346] A cellulose suspension was produced by milling cellulose in water in a ratio of 1.50:20 using 50 units of 10mm balls at 670RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0347] Collagen 1.25

[0348] The collagen was pre-milled and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0349] A collagen suspension was produced by milling pre-milled collagen in water in a ratio of 1.25:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0350] Collagen 1.50

[0351] The collagen was pre-milled and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 2 hours.

[0352] A collagen suspension was produced by milling pre-milled collagen in water in a ratio of 1.50:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 1 hour.

[0353] Alginate

[0354] An alginate suspension was produced by grinding alginate in water in a ratio of 1.00:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, whereby it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0355] Chitin

[0356] A chitin suspension was produced by grinding chitin in water in a ratio of 1.00:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0357] Chitosan

[0358] The chitosan was pre-milled and dried using a 10+1 alternating method with 30 units of 10 mm balls at 670 RPM where it was milled for 10 minutes followed by a 1 minute rest and then milled in the opposite direction for 10 minutes for a total of 1 hour.

[0359] A chitosan suspension was produced by milling pre-milled chitosan in water in a ratio of 1.50:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, totalling 1 hour.

[0360] Chitin Mineral Oil

[0361] A chitin suspension was produced by milling chitin in water with mineral oil in a ratio of 1.00:0.50:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0362] Chitin Beeswax

[0363] A chitin suspension was produced by grinding chitin in water in a ratio of 0.90:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, in which it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes for a total of 3 hours. Beeswax was added in a ratio of 0.50:0.90:20 and ground under the same conditions for 3 hours.

[0364] Chitin collagen silk

[0365] The collagen was pre-milled and dried using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 2 hours.

[0366] The fluffy silk was pre-milled and dried using a 10+1 alternation method with 50 units of 10 mm balls at 670 RPM, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 6 hours.

[0367] A chitin collagen silk suspension was produced by grinding chitin, collagen, and silk in water in a ratio of 0.70:0.15:0.15:20 with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0368] 2) Results

[0369] FIG. 33 shows the rheological polymer sweeps of each polymer suspension and its blends.

[0370] Example 14: Rheological effect of chitin pre-grinding The rheological effects of chitin suspensions were compared with the ratio and pre-milling effects. Chitin suspensions were prepared under the same conditions for ratios of 0.60, 0.80, 1.00 and 2.00, and the chitin was either used as is or pre-milled to reduce particle size.

[0371] No pre-grinding: Chitin suspensions were produced by grinding chitin in water in a ratio of 0.60:20 (or 0.8:20, or 1.00:20, or 2.00:20) with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, in which it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0372] With pre-milling: Chitin was pre-milled dry at 670 RPM with 50 units of 10 mm balls using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute break and then milled in the opposite direction for 10 minutes for a total of 3 hours. Chitin suspensions were produced by milling the pre-milled chitin in water at a ratio of 0.60:20 (or 0.8:20, or 1.00:20, or 2.00:20) with 50 units of 10 mm balls at 670 RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute break and then milled in the opposite direction for 10 minutes for a total of 3 hours.

[0373] As shown in Figure 34, the overall comparison indicates that pre-grinding reduces the final viscosity, regardless of the ratio of chitin used. Thus, these results show that the viscosity can be reduced by more than half by the pre-grinding step. This is highly advantageous as it allows for the inclusion of more material if desired, without affecting the final viscosity of the biopolymer suspension.

[0374] [Example 15: N-acetylglucosamine 1 HNMR] In general, the chitin suspensions described herein are composed of only chitin and water, and the extent of chitin degradation is expected to reach water-soluble forms of the polymer. To gain insight into the types of biopolymers present in the chitin formulations, 1 H NMR spectroscopy was performed, and preliminary results indicate the presence of water-soluble components with signatures that partially match the predicted spectra for monomeric and dimeric forms of chitin.

[0375] 1) Sample preparation

[0376] Two chitin suspensions were produced as follows: Chitin was milled in water at a ratio of 0.90:20 using 90 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 12 hours. The chitin suspension was then filtered under vacuum using a 3 μm Whatman™ filter to capture the water soluble components of the formulation.

[0377] The sample is then 1 HNMR spectroscopy, the filtrate was lyophilized, and the resulting solid was purified by D 2 The samples were resuspended in 0. An N-acetylglucosamine standard was also analyzed simultaneously.

[0378] 2) Results

[0379] Predicted Spectrum

[0380] As shown in Figure 35B, ChemDraw™ software (V16.0.1.49) was used to determine the N-acetylglucosamine (NAG; Figure 35A). 1 The predicted HNMR spectra were generated.

[0381] Comparison of NAG standards with aqueous filtrates from chitin suspensions

[0382] Two chitin suspensions (#1 and #2) were produced as follows. Briefly, chitin was milled in water at a ratio of 0.90:20 using 90 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 12 hours. The chitin suspension was then filtered under vacuum using a 3 μm Whatman™ filter to capture the water soluble components of the formulation. The two suspensions were then 1 The solutions were analyzed by H NMR spectroscopy. Similar overall spectra were observed for both replicates, indicating consistent production of water-soluble components by the described method (Figures 36A and 36B).

[0383] Next, chitin suspension #2 1 HNMR signatures were generated for N-acetylglucosamine standards. 1 The H NMR spectra were compared with those of the chitin suspensions of the present invention, and overall agreement was found between the spectra, as shown in Figure 36C, providing preliminary evidence for the presence of chitin monomer species and other water-soluble chitin components in the chitin suspensions of the present invention.

[0384] [Example 16: N-acetylglucosamine-doped chitin suspension] Since the chitin suspension of the present invention is inherently composed of long chains of N-acetylglucosamine, the stability of the suspension was investigated by adding N-acetylglucosamine monomers.

[0385] Chitin suspensions were produced by milling chitin and N-acetylglucosamine (NAG) at 670 RPM with 50 units of 10 mm balls in a ratio of a) 0.80:0.04:20 (i.e., 5% w / w NAG) or b) 0.80:0.08:20 (i.e., 10% w / w NAG) using a 10+1 alternation method, whereby this was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0386] Although not shown, the resulting chitin-NAG-water suspension was homogeneous and stable. These results demonstrate that N-acetylglucosamine monomers can be incorporated as an additive into chitin suspensions, thereby showing great promise for the addition of established anti-aging agents such as NAG to this formulation of the present invention.

[0387] [Example 17: Makeup Color Test] A study was conducted to test the ability of the biopolymer suspensions of the present invention to carry powders such as color additives and mica powder.

[0388] A chitin suspension was produced by grinding chitin in water in a ratio of 0.80:20 using 30 units of 10 mm balls at 670 RPM using a 10+1 alternation method, in which it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0389] Commercially available mica powders of various colors (e.g., bronze, mustard, cobalt, teal, mauve, red) were then added individually to the chitin suspension and mixed manually with a spatula. Quantities of mica ranging from 10 mg to 100 mg in 3 ml of suspension were prepared.

[0390] As an exemplary test, mica powders (100 mg) of various colors were uniformly suspended in a chitin preparation and then applied to the skin.

[0391] Although not shown, the preparation was found to dry evenly, was smooth to the touch, and did not flake. The intensity of the saturation was proportional to the amount of mica introduced into the suspension. The pigmented suspension washed off easily by rubbing with water without leaving a pigmented residue on the user's skin.

[0392] These results indicate that mica can be adequately suspended in chitin suspensions, validating the use of the biopolymer formulations of the present invention for make-up related cosmetic applications.

[0393] Example 18: Oil and wax biopolymer suspensions Biopolymer suspensions according to the invention were investigated for their ability to remain homogeneous in the presence of additives such as oils and waxes.

[0394] 1) Sample preparation

[0395] Chitin-mineral oil: Chitin suspension was produced by milling chitin in water with mineral oil in a ratio of 1.00:0.50:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0396] A chitin-beeswax:chitin suspension was produced by grinding chitin in water in a ratio of 0.90:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes for a total of 3 hours. Beeswax was added to the chitin suspension and then ground for an additional 3 hours to give a final chitin:beeswax:water ratio of 0.90:0.50:20.

[0397] Chitosan Additive: Chitosan was pre-milled dry at 670 RPM with 30 units of 10 mm balls using a 10+1 alternative where it was milled for 10 minutes, followed by a 1 minute pause, then milled in the opposite direction for 10 minutes for a total of 3 hours. Chitosan suspension was produced by milling chitosan in water at 670 RPM with 50 units of 10 mm balls using a 10+1 alternative where it was milled for 10 minutes, followed by a 1 minute pause, then milled in the opposite direction for 10 minutes for a total of 2 hours. Beeswax or mineral oil was added to the chitosan suspension and then milled for an additional 2 hours to obtain a final chitosan:beeswax:water or chitosan:mineral oil:water ratio of 1.20:0.50:20.

[0398] Cellulose additive: A cellulose suspension was produced by milling cellulose in water in a ratio of 1.00:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes for a total of 1 hour. Beeswax or mineral oil was added to the cellulose suspension and then milled for an additional hour to give a final cellulose:beeswax:water or cellulose:mineral oil:water ratio of 1.00:0.50:20.

[0399] Alginate Additive: Alginate suspensions were produced by milling alginate in water in a ratio of 2.00:20 with 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute pause, then milled in the opposite direction for 10 minutes for a total of 3 hours. Beeswax or mineral oil was added to the alginate suspension and then milled for an additional 3 hours to give a final alginate:beeswax:water or alginate:mineral oil:water ratio of 2.00:0.50:20.

[0400] Collagen additive: Collagen was pre-milled dry using 50 units of 10mm balls at 670RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute pause, then milled in the opposite direction for 10 minutes, for a total of 3 hours. Collagen suspension was produced by milling collagen in water at a ratio of 1.00:20 using 50 units of 10mm balls at 670RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute pause, then milled in the opposite direction for 10 minutes, for a total of 3 hours. Beeswax or mineral oil was added to the collagen suspension and then milled for an additional 3 hours to obtain a final collagen:beeswax:water or collagen:mineral oil:water ratio of 1.00:0.50:20.

[0401] Silk Additive: Silk was pre-ground dry using 50 units of 10mm balls at 670RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute pause and then milled in the opposite direction for 10 minutes for a total of 3 hours. Silk suspension was produced by milling silk in water using 50 units of 10mm balls at 670RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute pause and then milled in the opposite direction for 10 minutes for a total of 6 hours. Beeswax or mineral oil was added to the silk suspension and then milled for an additional 3 hours to obtain a final silk:beeswax:water or silk:mineral oil:water ratio of 1.00:0.50:20.

[0402] 2) Results

[0403] The resulting biopolymer-added water suspensions were stable and uniform for the chitin, chitosan, cellulose, alginate, collagen and silk blends. All the resulting blends provided smooth application to the skin (data not shown). These results confirm that the biopolymer suspensions according to the present invention can successfully incorporate additives.

[0404] Example 19: Preparation of ginseng suspension A ginseng suspension was produced by milling ginseng powder in water in a ratio of 1.00:20 with 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, totalling 1 hour.

[0405] As depicted in (Erreur! Source du renvoi introuvable.and 2), ginseng powder was not soluble in water, but milling produced a stable homogeneous suspension. It was also possible to decrease the viscosity of the milled suspension by increasing the shear rate, as detailed in Table 6.

[0406] Table 6: Viscosity of suspended carrots [Table 6]

[0407] [Example 20: Preparation of additive-containing suspension] Separation is frequently a problem when making biopolymer suspensions because some water can separate out at the top of the suspension due to particle aggregation and binding. Emulsifiers typically help keep the oil and water phases together.

[0408] Different additives were tested for their potential to solve any possible separation problems in the biopolymer suspension of the present invention.

[0409] The samples were evaluated for separation, aggregate formation, and viscosity. Samples that did not show separation after suspension were tested in a separation test of centrifugation at 4000 RPM for 10 minutes. The following additives were added to the cellulose suspension: cetyl alcohol, glyceryl stearate, PC90, PSC3, PEG, guar, xanthan gum, agarose, sodium hyaluronate, Tween 80™, glycerin (humectant).

[0410] 1) Cellulose

[0411] 1.1)Tween 80(trademark)

[0412] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:1.25:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0413] Results: Phase separation: <1 mL; aggregate formation: none; color change: none, still white; viscosity: see Table 7.

[0414] Table 7: Viscosity of cellulose suspensions containing Tween 80™ additive [Table 7]

[0415] 1.2) Glyceryl stearate

[0416] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:1.25:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0417] Results: Phase separation: none; aggregate formation: none; color change: none, still white; viscosity: see Table 8.

[0418] Table 8: Viscosity of cellulose suspensions with glyceryl stearate additive [Table 8]

[0419] 1.3) Cetyl alcohol

[0420] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:1.25:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0421] Results: Phase separation: <1 mL; aggregate formation: none; color change: none, still white; viscosity: see Table 9.

[0422] Table 9: Viscosity of cellulose suspensions with cetyl alcohol additive [Table 9]

[0423] 1.4) Sodium Hyaluronate

[0424] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:1.25:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0425] Results: Phase separation: none; aggregate formation: none; color change: light gray, still white; viscosity: too high to be measured with our Brookfield viscometer equipped with spindle and chamber (max 1 MmPa·s).

[0426] Another cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:0.2:20 using 50 units of 10mm balls at 670 RPM using a 10+1 alternative method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0427] Results: Phase separation: none; aggregate formation: none; color change: none, still white; viscosity: see Table 10. Table 10: Viscosity of cellulose suspensions with sodium hyaluronate additive [Table 10]

[0428] 1.5) PSC3

[0429] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:1.25:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0430] Results: Phase separation: none; aggregate formation: none; color change: none, still white; viscosity: see Table 11.

[0431] Table 11: Viscosity of cellulose suspensions with PSC3 additive [Table 11]

[0432] 1.6) PC90

[0433] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:1.30:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0434] Results: Phase separation: ~2mL; Aggregate formation: None; Color change: None, still white; Viscosity: See Table 12.

[0435] Table 12: Viscosity of cellulose suspensions with PC90 additive [Table 12]

[0436] 1.7) Agarose

[0437] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:0.5:20 using 50 units of 10mm balls at 670RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0438] Results: Phase separation: none; aggregate formation: none; color change: light gray; viscosity: too high to be measured with our Brookfield viscometer equipped with the spindle and chamber (max 1 MmPa·s).

[0439] Another cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:0.2:20 using 50 units of 10mm balls at 670 RPM using a 10+1 alternative method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0440] Results: Phase separation: none; aggregate formation: none; color change: none, still white; viscosity: too high to be measured with our Brookfield viscometer equipped with spindle and chamber (max 1 MmPa·s).

[0441] 1.8) Xanthan gum

[0442] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:0.5:20 using 50 units of 10mm balls at 670RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0443] Results: Phase separation: none; aggregate formation: none; color change: none, still white; viscosity: see Table 13.

[0444] Table 13: Viscosity of cellulose suspensions with xanthan gum additive [Table 13]

[0445] Another cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:0.2:20 using 50 units of 10mm balls at 670 RPM using a 10+1 alternative method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0446] Results: Phase separation: none; aggregate formation: none; color change: none, still white; viscosity: see Table 14.

[0447] Table 14: Viscosity of cellulose suspensions with xanthan gum additive [Table 14]

[0448] 1.9) PEG20K

[0449] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:0.5:20 using 50 units of 10mm balls at 670RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0450] Results: Phase separation: <1 mL; aggregate formation: none; color change: none, still white; viscosity: see Table 15.

[0451] Table 15: Viscosity of cellulose suspensions containing PEG20K additive [Table 15]

[0452] 1.10) Glycerin

[0453] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:1.25:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0454] Results: Phase separation: <1 mL; aggregate formation: none; color change: none, still white; viscosity: see Table 16.

[0455] Table 16: Viscosity of cellulose suspensions with glycerin additive [Table 16]

[0456] 1.11) Guar

[0457] A cellulose suspension was produced by milling cellulose in water at a cellulose to additive to water ratio of 1.5:0.15:20 using 50 units of 10mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0458] Results: Phase separation: none; aggregate formation: none; color change: grey; viscosity: see Table 17.

[0459] Table 17: Viscosity of cellulose suspensions with guar additive [Table 17]

[0460] 2) Chitin

[0461] 2.1) Cetyl alcohol

[0462] A chitin suspension was produced by grinding chitin in water at 670 RPM with 50 units of 10 mm balls at a chitin to water ratio of 1:20 using a 10+1 substitution method, in which it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes for a total of 3 hours. Cetyl alcohol was added to create a chitin to cetyl alcohol to water ratio of 1:1.25:20, and then ground under the same conditions for 3 hours.

[0463] Results: Phase separation: ~2 mL; Aggregate formation: None; Color change: Light gray; Viscosity: See Table 18.

[0464] Table 18: Viscosity of chitin suspensions with cetyl alcohol additive [Table 18]

[0465] 2.2) Glyceryl stearate

[0466] A chitin suspension was produced by grinding chitin in water at 670 RPM with 50 units of 10 mm balls at a chitin to water ratio of 1:20 using a 10+1 alternative method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes for a total of 3 hours. Cetyl alcohol was added to create a chitin to glyceryl stearate to water ratio of 1:1.25:20, then ground under the same conditions for 3 hours.

[0467] Results: Phase separation: none; aggregate formation: none; color change: none, still white; viscosity: see Table 19.

[0468] Table 19: Viscosity of chitin suspensions with glyceryl stearate additive [Table 19]

[0469] 3) Chitosan

[0470] 3.1) Cetyl alcohol

[0471] Chitosan was pre-milled dry at 670 RPM with 30 units of 10 mm balls using a 10+1 alternative where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes for a total of 3 hours. Chitosan suspension was produced by milling chitosan in water at 670 RPM with 50 units of 10 mm balls using a 10+1 alternative where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes for a total of 3 hours. Cetyl alcohol was added to create a chitosan to cetyl alcohol to water ratio of 1:1.25:20, then milled under the same conditions for 3 hours.

[0472] Results: Phase separation: none; aggregate formation: none; color change: none, still off-white; viscosity: see Table 20.

[0473] Table 20: Viscosity of chitosan suspensions with cetyl alcohol additive [Table 20]

[0474] 3.2) Glyceryl stearate

[0475] Chitosan was pre-milled dry at 670 RPM with 30 units of 10 mm balls using a 10+1 alternative where it was milled for 10 minutes, followed by a 1 minute pause, then milled in the opposite direction for 10 minutes for a total of 3 hours. Chitosan suspension was produced by milling chitosan in water at 670 RPM with 50 units of 10 mm balls using a 10+1 alternative where it was milled for 10 minutes, followed by a 1 minute pause, then milled in the opposite direction for 10 minutes for a total of 3 hours. Glyceryl stearate was added to create a chitosan to glyceryl stearate to water ratio of 1:1.25:20 and then milled under the same conditions for 3 hours.

[0476] Results: Phase separation: none; aggregate formation: none; color change: none, still off-white; Viscosity: see Table 21.

[0477] Table 21: Viscosity of chitosan suspensions with glyceryl stearate additive [Table 21]

[0478] 4) Centrifugal separation test

[0479] The samples were centrifuged at 4000 RPM for 10 minutes. The results were as follows: Cellulose containing glyceryl stearate <200μL separated Cellulose containing cetyl alcohol ~5mL isolated Cellulose containing PSC3, no separation Cellulose with xanthan gum, no separation Cellulose containing sodium hyaluronate, no separation Cellulose containing sodium hyaluronate, separates not only water but also gel ~6mL Chitin containing cetyl alcohol, ~4mL isolated Chitin with glyceryl stearate, no separation Chitosan with cetyl alcohol, ~2mL isolated; Chitosan containing glyceryl stearate, ~2mL isolated

[0480] conclusion

[0481] Some additives appear to be suitable to reduce or eliminate any phase separation that may be observed in the original water and biopolymer formulation. Glyceryl stearate, cetyl alcohol, tara gum, sodium hyaluronate, PSC3, xanthan gum, and guar appear to stabilize the suspension with the appropriate amounts of additives used. The overall viscosity of the formulations containing additives was observed to increase significantly, which could be mitigated by the addition of other additives. Further separation tests by centrifugation (4000 RPM for 10 minutes) showed that the blends of glyceryl stearate, PSC3, xanthan gum, and sodium hyaluronate persisted in their stable state.

[0482] [Example 21: Floral suspension] Lavender, chrysanthemum, rosebud, jasmine and calendula flowers were converted into a suspension containing only flowers and water.

[0483] For all samples herein, the flowers were obtained in a dried state. The dried flowers were ground into smaller particles in a blade grinder for 30 seconds.

[0484] To produce a fine powder, the dried ground flower particles were pre-milled using a 10+1 alternation method with 50 units of 10 mm balls at 670 RPM, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 1 hour.

[0485] A floral suspension was produced by grinding floral powder in water in a ratio of 2.00:20 using 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, whereby it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, totalling 1 hour.

[0486] 1) Lavender: Appearance of suspension: uniform dark green. Viscosity: See Table 22.

[0487] Table 22: Viscosity of Lavender Suspension 2:20 [Table 22]

[0488] 2) Chrysanthemum: Appearance of suspension: homogeneous dark beige. Viscosity: See Table 23.

[0489] Table 23: Viscosity of Chrysanthemum Suspension 2:20 [Table 23]

[0490] 3) Rosebud: Suspension appearance: homogeneous yellow / beige. Viscosity: See Table 24.

[0491] Table 24: Viscosity of Rosebud Suspension 2:20 [Table 24]

[0492] 4) Jasmine: Appearance of suspension: homogeneous brown. Viscosity: See Table 25.

[0493] Table 25: Viscosity of Jasmine Suspension 2:20 [Table 25]

[0494] 5) Calendula: Appearance of suspension: uniform dark mustard. Viscosity: See Table 26.

[0495] Table 26: Viscosity of Calendula Suspension 2:20 [Table 26]

[0496] Conclusion: Advantageously, dried flowers may be a suitable material for producing a uniform suspension with suitable viscosity. The overall aroma immediately after production is still pleasant. A preservative may be preferred to stabilize the suspension for long-term storage.

[0497] [Example 22: Freeze / thaw pretreatment] Freezing / thawing was tested as a pretreatment technique before grinding because it has the potential to disrupt hydrogen bonds between polymer chains, thereby increasing swelling of the biopolymer.

[0498] The biopolymer was wetted and then frozen at -15°C for 10 hours and then thawed. This freeze / thaw cycle was repeated twice. The treated biopolymer was then ground and suspended.

[0499] The biopolymer was combined with at least enough water until it was wet and saturated. The mixture was frozen at -15°C for 10 hours and then thawed. This freeze / thaw cycle was repeated twice. The treated biopolymer was then ground and suspended. Visual observations were noted for the following: phase separation, formation of aggregates, color change and viscosity.

[0500] 1) Chitin

[0501] The frozen pretreatment of the chitin mixture was prepared with additional water to create a suspension in a ratio of 1:20. The mixture was milled at 670 RPM with 50 units of 10 mm balls using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0502] Results: Phase separation: none; aggregate formation: none; color change: beige to off-white; viscosity: see Table 27.

[0503] Table 27: Viscosity of chitin suspensions after freeze / thaw pretreatment [Table 27]

[0504] 2) Chitosan

[0505] A freeze pretreatment of the chitosan mixture was prepared with additional water to create a suspension in a ratio of 1.30:20. The mixture was milled at 670 RPM with 50 units of 10 mm balls using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0506] Results: Phase separation: none; aggregate formation: none; color change: beige to white; viscosity: see Table 28.

[0507] Table 28: Viscosity of chitosan suspensions after freeze / thaw pretreatment [Table 28]

[0508] 3) Cellulose

[0509] The frozen pretreatment of the cellulose mixture was prepared with additional water to create a suspension in a ratio of 1:20. The mixture was milled at 670 RPM with 50 units of 10 mm balls using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0510] Results: Phase separation: none; aggregate formation: none; color change: none; viscosity: see Table 29.

[0511] Table 29: Viscosity of cellulose suspensions after freeze / thaw pretreatment [Table 29]

[0512] conclusion

[0513] Freezing pretreatment had a ~18% decrease in the viscosity of chitin, a 115% increase in the viscosity of chitosan, and a ~25% increase in the viscosity of cellulose. The increase in viscosity may be the result of polymer separation, while the decrease in viscosity may be the result of polymer chain scission.

[0514] Example 23: Low energy milling of suspensions of chitin, chitosan and cellulose. Particle size at the crossroads of biopolymer suspensions was investigated using low-energy milling, which allowed for particle size analysis of poorly suspended samples and identification of changes in particle or fiber morphology.

[0515] The analysis was carried out by grinding at low RPM. Aliquots were removed during the grinding process at different time intervals. Horiba particle size analysis and SEM imaging were used to analyze particle size and morphology, respectively.

[0516] The biopolymers were suspended in a planetary mill at 10 units 10 mm at 200 and 400 RPM in a ratio of 1:20 for chitin, 1.30:20 for chitosan, and 1.5:20 for cellulose.

[0517] 1) Chitin

[0518] Chitin was milled at different powers for different durations to ascertain the effect on suspension and particle size. Chitin particle size was also measured in water after production of unmilled and fully suspended versions. Table 30 summarizes the results and milling conditions are listed in the following sections.

[0519] Table 30: Particle size of chitin under different grinding conditions [Table 30]

[0520] 1.1) Chitin grinding at 200 RPM (C18)

[0521] Chitin suspensions were generated by grinding chitin in water with 10 units of 10 mm balls at 200 RPM with a chitin to water ratio of 1:20 in 10 min increments, where aliquots were removed for imaging at 10, 20, 30, 60, and 180 min.

[0522] Appearance of the suspension: Fluffy polymer but separated, not completely suspended. Particle size analysis: Number average particle size 181.8 μm; Particle size range: 11.00-418.6 μm. Measurement details are shown in Figure 38A and Table 31. SEM imaging is shown in Figure 38B, the picture shows some larger particles with smaller agglomerated particles. Table 31: Particle size analysis of chitin grinding at 200 RPM (C18) [Table 31]

[0523] 1.2) Chitin grinding at 400 RPM (C6)

[0524] Chitin suspensions were generated by grinding chitin in water with 10 units of 10 mm balls at 400 RPM in a chitin to water ratio of 1:20 in 10 min increments, where aliquots were removed for imaging at 10, 30, and 60 min.

[0525] Appearance of suspension: partially suspended, ~15% separated. Particle size analysis: number average particle size 172.2 μm; particle size range: 9.25-418.6 μm. Measurement details are shown in Figure 39A and Table 32. SEM imaging is shown in Figure 39B.

[0526] Table 32: Particle size analysis of chitin grinding at 400RPM (C6) [Table 32]

[0527] 1.3) No chitin crushing (C0)

[0528] For reference, particle size analysis of water and chitin was performed. Chitin and water were combined in a 1:20 ratio without any grinding.

[0529] Particle size analysis: number average particle size 218.7 μm; particle size range: 15.56-418.6 μm. The measurement details are shown in Figure 40 and Table 33.

[0530] Table 33: Particle size analysis of chitin without grinding (C0) [Table 33]

[0531] 1.4) Chitin standard grinding (CF)

[0532] A chitin suspension was produced by grinding chitin in water using 50 units of 10 mm balls at 670 RPM with a chitin to water ratio of 1.00:20 using a 10+1 substitution method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0533] Appearance of the suspension: completely suspended. Particle size analysis: number average particle size 110.3 μm; particle size range: 1.156-74 μm. The measurement details are shown in Figure 41 and Table 34.

[0534] Table 34: Particle size analysis of chitin standard grind (CF) [Table 34]

[0535] 2) Chitosan

[0536] Chitosan was milled at different powers for different times to see the effect on suspension and particle size. The particle size of chitosan was also measured in water as a non-milled and fully suspended version. Table 35 summarizes the results with the milling conditions listed below.

[0537] Table 35: Particle size of chitosan under different grinding conditions [Table 35]

[0538] 1.1) Chitosan grinding at 200 RPM (B18)

[0539] Chitosan suspensions were generated by milling chitosan in water with 10 units of a 10 mm ball at 200 RPM in a chitosan to water ratio of 1.3:20 in 10 min increments, where aliquots were removed for imaging at 10, 20, 30, 60 and 180 min.

[0540] Appearance of the suspension: Fluffy polymer but separated, not completely suspended. Particle size analysis: Number average particle size 92.78 μm; Particle size range: 5.50-248.9 μm. Measurement details are shown in Figure 42A and Table 36. SEM imaging is shown in Figure 42B, the photo shows small nano-sized particles.

[0541] Table 36: Particle size analysis of chitosan grinding at 200 RPM (B18) [Table 36]

[0542] 2.2) Chitosan grinding at 400 RPM (B6)

[0543] Chitosan suspensions were generated by milling chitosan in water with 10 units of a 10 mm ball at 400 RPM in a chitosan to water ratio of 1:20 in 10 min increments, where aliquots were removed for imaging at 10, 30, and 60 min.

[0544] Appearance of suspension: partially suspended, ~15% separated. Particle size analysis: number average particle size 95.83 μm; particle size range: 7.78-296 μm. Measurement details are shown in Figure 43A and Table 37. SEM imaging is shown in Figure 43B, the photo shows nano-sized particles.

[0545] Table 37: Particle size analysis of chitosan grinding at 400 RPM (B6) [Table 37]

[0546] 2.3) Chitosan without crushing (B0)

[0547] For reference, particle size analysis of water and chitosan was performed. Chitosan and water were combined in a 1:20 ratio without any milling.

[0548] Number average particle size: 65.76 μm. Particle size range: 7.78 to 248.9 μm. Measurement details are shown in Figure 44 and Table 38.

[0549] Table 38: Particle size analysis of chitosan without milling (B0) [Table 38]

[0550] 2.4) Chitosan standard grinding (BF)

[0551] Chitosan was pre-milled dry using 30 units of 10 mm balls at 670 RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute break and then milled in the opposite direction for 10 minutes for a total of 3 hours. CXC chitosan suspension was produced by milling chitosan in water using 50 units of 10 mm balls at 670 RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute break and then milled in the opposite direction for 10 minutes for a total of 3 hours.

[0552] Appearance of the suspension: completely suspended. Particle size analysis: number average particle size 32.99 μm; particle size range: 3.89-148.0 μm. The measurement details are shown in Figure 45 and Table 39.

[0553] Table 39: Particle size analysis of chitosan standard grind (BF) [Table 39]

[0554] 3) Cellulose

[0555] To see the effect on suspension and particle size, cellulose was milled at different powers for different times. The particle size of cellulose was also measured in water as unmilled and fully suspended version. Table 40 summarizes the results under the milling conditions listed below.

[0556] Table 40: Particle size of cellulose under different grinding conditions [Table 40]

[0557] 3.1) Cellulose grinding at 200 RPM (A18)

[0558] A cellulose suspension was generated by grinding cellulose in water with 10 units of 10 mm balls at 200 RPM in a cellulose to water ratio of 1:20 in 10 min increments, where aliquots were removed for imaging at 10, 20, 30, 60, and 180 min.

[0559] Appearance of the suspension: Fluffy polymer but separated, not completely suspended. Particle size analysis: Number average particle size 81.19 μm; Particle size range: 9.25-296 μm. Measurement details are shown in Figure 46A and Table 41. SEM imaging is shown in Figure 46B, the picture shows large fibers with widths ranging from 20 to 62 μm.

[0560] Table 41: Particle size analysis of cellulose grinding at 200 RPM (A18) [Table 41]

[0561] 3.2) Cellulose grinding at 400 RPM (A6)

[0562] A cellulose suspension was generated by grinding cellulose in water with 10 units of 10 mm balls at 400 RPM in a cellulose to water ratio of 1:20 in 10 min increments, where aliquots were removed for imaging at 10, 30, and 60 min.

[0563] Appearance of suspension: partially suspended, ~15% separated. Particle size analysis: Number average particle size: 82.72 μm. Particle size range: 7.72-296 μm. Measurement details are shown in Figure 47A and Table 42. An SEM image is shown in Figure 47B, the picture shows large fibers with widths ranging from 4 to 16 μm.

[0564] Table 42: Particle size analysis of cellulose grinding at 400 RPM (A6) [Table 42]

[0565] 3.3) No cellulose grinding (A0)

[0566] For reference, particle size analysis of water and cellulose was performed. Cellulose and water were combined in a 1:20 ratio without any grinding.

[0567] Appearance of the suspension: completely separated. Particle size analysis: number average particle size 82.83 μm; particle size range: 11-296 μm. The measurement details are shown in Figure 48 and Table 43.

[0568] Table 43: Particle size analysis of cellulose without milling (A0) [Table 43]

[0569] 3.4) Cellulose standard grinding (AF)

[0570] A CXC cellulose suspension was produced by milling cellulose in water at a cellulose to water ratio of 1.00:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0571] Appearance of the suspension: completely suspended. Particle size analysis: number average particle size: 1.117 μm; particle size range: 0.578-124.5 μm. The measurement details are shown in Figure 49 and Table 44.

[0572] Table 44: Particle size analysis of cellulose standard grind (AF) [Table 44]

[0573] conclusion

[0574] Overall, there appears to be a maximum particle size of the biopolymer that, when reduced, produces a suspension.

[0575] Example 24: Incorporation of oil into chitin-chitosan and cellulose suspensions.

[0576] In cosmetics, the inclusion of oil is common. The stability of the mixture can be affected by the amount of oil added to the system. A substrate that can accommodate a large amount of oil improves application and reduces the amount of emulsifier required to maintain the integrity of the suspension.

[0577] For biopolymer suspensions, the amount of oil was varied from 10% of the total liquid content to test the effect of total oil concentration on suspension stability. Suspensions were prepared using a planetary mill.

[0578] Biopolymers were suspended in a planetary mill in a ratio of 1:20 for chitin, 1.30:20 for chitosan, and 1.5:20 for cellulose, varying the liquid content from 90% water / 10% oil to 50% water / 50% oil.

[0579] The viscosity of the samples was measured using a Brookfield RVDVNX rheometer. Visual observations were noted for the following: phase separation, aggregate formation, and color change.

[0580] 1) Chitin containing oil

[0581] Chitin suspensions were produced by grinding chitin in water in ratios of 1:18:2 (10% oil), 1:16:4 (20% oil), 1:14:6 (30% oil), 1:12:8 (40% oil) or 1:10:10 (50% oil) with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, whereby it was ground for 10 minutes, followed by a 1 minute rest and then 10 minutes of grinding in the opposite direction for a total of 3 hours.

[0582] 1.1) 10% chitin oil in water

[0583] Results: Phase separation: none. Agglomerate formation: homogeneous in appearance. Color: off-white. Viscosity: see Table 45.

[0584] Table 45: Viscosity of suspension of chitin 10% oil in water [Table 45]

[0585] 1.2) 20% chitin oil in water

[0586] Results: Phase separation: minor, ~30 μL. Aggregate formation: homogeneous in appearance. Color: off-white. Viscosity: see Table 46. viscosity:

[0587] Table 46: Viscosity of suspension of chitin 20% oil in water [Table 46]

[0588] 1.3) 30% chitin oil in water

[0589] Results: Phase separation: minor, ~30 μL. Aggregate formation: homogeneous in appearance. Color: off-white. Viscosity: see Table 47.

[0590] Table 47: Viscosity of suspension of chitin 30% oil in water [Table 47]

[0591] 2) Chitosan containing oil

[0592] Chitosan suspensions were produced by milling chitosan in water in ratios of 1:18:2 (10% oil), 1:17:3 (15% oil), or 1:16:4 (20% oil) with 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0593] 2.1) Chitosan 10% oil in water

[0594] Results: Phase separation: none. Agglomerate formation: homogeneous in appearance. Color: off-white / beige. Viscosity: see Table 48.

[0595] Table 48: Viscosity of Chitosan 10% Oil in Water Suspension [Table 48]

[0596] 2.2) Chitosan 15% oil in water

[0597] Results: Phase separation: none. Agglomerate formation: homogeneous in appearance. Color: light gray. Viscosity: see Table 49.

[0598] Table 49: Viscosity of chitosan oil in water suspension [Table 49]

[0599] 2.3) Chitosan 20% oil in water

[0600] Results: Phase separation: small amount ~ 1 mL; Aggregate formation: homogeneous appearance. Color: light gray. Viscosity: see Table 50.

[0601] Table 50: Viscosity of Chitosan 20% Oil in Water Suspension [Table 50]

[0602] 3) Cellulose containing oil

[0603] CXC cellulose suspensions were produced by milling cellulose in water in ratios of 1:18:2 (10% oil), 1:16:4 (20% oil), 1:14:6 (30% oil), 1:12:8 (40% oil) or 1:10:10 (50% oil) with 50 units of 10mm balls at 670 RPM using a 10+1 alternation method, whereby it was milled for 10 minutes, followed by a 1 minute rest and then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0604] 3.1) Cellulose 10% oil in water

[0605] Results: Phase separation: none. Agglomerate formation: homogeneous in appearance. Color: white. Viscosity: see Table 51.

[0606] Table 51: Viscosity of cellulose 10% oil in water suspension [Table 51]

[0607] 3.2) Cellulose 20% oil in water

[0608] Results: Phase separation: none. Agglomerate formation: homogeneous in appearance. Color: white. Viscosity: see Table 52.

[0609] Table 52: Viscosity of cellulose 20% oil in water suspension [Table 52]

[0610] 3.3) Cellulose 30% oil in water

[0611] Results: Phase separation: none. Agglomerate formation: homogeneous appearance. Color: white. Viscosity: see Table 53.

[0612] Table 53: Viscosity of suspension of cellulose 30% oil in water [Table 53]

[0613] 3.4) Cellulose 40% oil in water

[0614] Results: Phase separation: none. Agglomerate formation: uniform appearance; Color: white. Viscosity: see Table 54.

[0615] Table 54: Viscosity of cellulose 40% oil in water suspension [Table 54]

[0616] conclusion

[0617] The incorporation of oil into chitin, chitosan and cellulose suspensions is possible up to significant amounts, above 10%. Chitin was stable up to at least 30% oil; chitosan was stable up to at least 20% oil and cellulose was stable up to at least 40% oil. This indicates the emulsifying ability of the polymers as Pickering factors.

[0618] Example 25: Extent of chitin, chitosan, and cellulose incorporation in suspensions

[0619] Tests were conducted to help define the possible range of biopolymer incorporation into the suspension. This was achieved by starting with a high biopolymer to water ratio followed by increasing amounts of biopolymer until a non-uniform suspension appeared, i.e. the presence of non-suspended particles or viscosity that prevented processing with the planetary mill (clumping with the balls in the jar). Homogeneity and smoothness were further evaluated.

[0620] 1) Chitin

[0621] Chitin suspensions were produced by grinding chitin in water at either a 3:20, 4:20, or 5:20 chitin to water ratio using 50 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was ground for 10 minutes, followed by a 1 minute rest, then 10 minutes grinding in the opposite direction for a total of 3 hours. The results are shown in Table 55.

[0622] Table 55: Appearance of various chitin suspensions [Table 55]

[0623] 2) Chitosan

[0624] Chitosan was pre-milled and dried using 30 units of 10 mm balls at 670 RPM using a 10+1 alternative where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes for a total of 3 hours. Chitosan suspensions were produced by milling chitosan in water at 670 RPM using 50 units of 10 mm balls at chitosan to water ratios of 3:20, 4:20, or 5:20 using a 10+1 alternative where it was milled for 10 minutes, followed by a 1 minute break, then milled in the opposite direction for 10 minutes for a total of 3 hours. The results are shown in Tables 56 and 57.

[0625] Table 56: Appearance of various chitosan suspensions [Table 56]

[0626] Table 57: Viscosity 3:20 Chitosan:Water Suspension [Table 57]

[0627] 3) Cellulose

[0628] Cellulose suspensions were produced by milling cellulose in water at 3:20, 4:20, or 5:20 cellulose to water ratios with 50 units of 10 mm balls at 670 RPM using a 10+1 alternative method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours. The results are shown in Table 58.

[0629] Table 58: Appearance of various cellulose suspensions [Table 58]

[0630] conclusion

[0631] For all three biopolymers tested - chitin, chitosan and cellulose - suspension occurs at biopolymer to water ratios of at least 3:20, at least 4:20, or at least 5:20.

[0632] Example 26: pH stability of chitin, chitosan, and cellulose

[0633] In cosmetics, the pH of ingredients and mixtures can vary. A base that can accommodate a wide pH range improves application.

[0634] Therefore, tests were conducted to help define the possible range of pH. To do so, the pH biopolymer suspension was changed to extremes, i.e., low and high pH, ​​and the effect on the stability of the suspension was tested. The pH of the suspension mixture was measured with pH paper. Visual observations were made for the following: phase separation, formation of aggregates, and color change.

[0635] 1) Chitin (starting pH: 6-7)

[0636] 1.1) Chitin acid test

[0637] A chitin suspension was produced by grinding chitin in water using 50 units of 10 mm balls at 670 RPM with a chitin to water ratio of 1.00:20 using a 10+1 substitution method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes, for a total of 3 hours.

[0638] Chitin suspension (6.08 g) and 1 M HCl (5.45 g) were combined and vortexed for 20 seconds. Results: Phase separation: none; aggregate formation: none; color change: none; final pH: ~1.

[0639] 1.2) Chitin base test

[0640] The chitin suspension (6.15 g) and 1 M NaOH (5.09 g) were combined and vortexed for 20 seconds. Results: Phase separation: none; aggregate formation: none; color change: none; final pH: >12.

[0641] 2) Chitosan (starting pH: 7-8)

[0642] The chitosan was pre-milled and dried using 30 units of 10 mm balls at 670 RPM using a 10+1 alternation method, where it was milled for 10 minutes, followed by a 1 minute stop and then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0643] A chitosan suspension was produced by milling chitosan in water using a 10+1 alternating method with 50 units of 10 mm balls at 670 RPM with a chitosan to water ratio of 1.00:20, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0644] 2.1) Chitosan acid test

[0645] The chitosan suspension (6.03 g) and 1 M HCl (5.11 g) were combined and vortexed for 20 seconds. Results: Phase separation: none; aggregate formation: none; color change: opaque translucent off-white; final pH: ~1.

[0646] 2.2) Chitosan base test

[0647] The chitosan suspension (6.08 g) and 1 M NaOH (5.01 g) were combined and vortexed for 20 seconds. Results: Phase separation: none; aggregate formation: none; color change: none; final pH: >12.

[0648] 3) Cellulose (starting pH: 6-7)

[0649] A cellulose suspension was produced by milling cellulose in water at a cellulose to water ratio of 1.00:20 using 50 units of 10 mm balls at 670 RPM using a 10+1 substitution method, whereby it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes, for a total of 3 hours.

[0650] 3.1) Cellulose acid test

[0651] The cellulose suspension (6.12 g) and 1 M HCl (5.24 g) were combined and vortexed for 20 seconds. Results: Phase separation: none; aggregate formation: none; color change: none; final pH: ~1.

[0652] 3.2) Cellulose base test

[0653] The cellulose suspension (6.01 g) and 1 M NaOH (5.04 g) were combined and vortexed for 20 seconds. Results: Phase separation: none; aggregate formation: none; color change: none; final pH: >12.

[0654] conclusion

[0655] All samples appear to be stable (i.e., do not separate) over the pH range of 1 to 12. The chitosan suspensions with acid changed from solid opaque suspensions to translucent opaque suspensions, which is expected since chitosan did not form a clear dissolved polymer solution but does dissolve in acid.

[0656] Example 27: Complete formulation of chitin, chitosan, and cellulose suspensions.

[0657] A complete formulation of the biopolymer suspension was generated, including additives for preservation and emulsification. The stability of the formulation was further tested by the addition of mineral oil.

[0658] For all specific examples listed below, 1) benzoic acid was used as a preservative; 2) glyceryl stearate and cetyl alcohol were used as emulsifiers; 3) a centrifuge separation test was performed to test for phase separation of water from the biopolymer suspension phase; and 4) the viscosity of the final composition was measured.

[0659] 1) Chitin

[0660] 1.1) Chitin containing emulsifiers and preservatives

[0661] A chitin suspension was produced by grinding chitin in water using 50 units of 10mm balls at 670 RPM with a chitin to water ratio of 1.00:20 using a 10+1 substitution method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes for a total of 3 hours. Glyceryl stearate and benzoic acid were added to create a chitin to glyceryl stearate to benzoic acid to water ratio of 1:1.25:0.10:20, then ground under the same conditions for 3 hours.

[0662] The viscosity of the suspension is shown in Figure 50. Separation testing by centrifugation at 4000 RPM for 10 minutes showed some separation of ~100 μL.

[0663] 1.2) Chitin containing emulsifiers, preservatives and oils

[0664] A chitin suspension was produced by grinding chitin in water using 50 units of 10mm balls at 670 RPM with a chitin to water ratio of 1.00:20 using a 10+1 substitution method, where it was ground for 10 minutes, followed by a 1 minute rest, then grinding in the opposite direction for 10 minutes for a total of 3 hours. Glyceryl stearate and benzoic acid were added to create a chitin to glyceryl stearate to benzoic acid to water ratio of 1:1.25:0.10:20, then ground under the same conditions for 3 hours.

[0665] Mineral oil was added at a final ratio of chitin to glyceryl stearate to benzoic acid to mineral oil to water of 1:1.25:0.10:0.50:20, followed by milling under the same conditions for 3 hours.

[0666] The viscosity of the suspension is shown in Figure 50. Separation testing by centrifugation at 4000 RPM for 10 minutes showed some separation of ~0.5 mL.

[0667] 2) Chitosan

[0668] 2.1) Chitosan with emulsifiers and preservatives

[0669] Chitosan was pre-milled dry using 30 units of 10mm balls at 670RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute pause and then milled in the opposite direction for 10 minutes for a total of 3 hours. CXC chitosan suspension was produced by milling chitosan in water using 50 units of 10mm balls at 670RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute pause and then milled in the opposite direction for 10 minutes for a total of 3 hours. Glyceryl stearate and benzoic acid were added to create a chitosan to glyceryl stearate to benzoic acid to water ratio of 1.30:1.25:0.10:20 and then milled under the same conditions for 3 hours.

[0670] The viscosity was too high to measure with a Brookfield™ viscometer. A centrifuge separation test, 10 minutes, 4000 RPM, showed no separation.

[0671] 2.2) Chitosan with emulsifiers, preservatives and oils

[0672] Chitosan was pre-milled dry using 30 units of 10mm balls at 670RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute pause and then milled in the opposite direction for 10 minutes for a total of 3 hours. CXC chitosan suspension was produced by milling chitosan in water using 50 units of 10mm balls at 670RPM using a 10+1 alternative where it was milled for 10 minutes followed by a 1 minute pause and then milled in the opposite direction for 10 minutes for a total of 3 hours. Glyceryl stearate and benzoic acid were added to create a chitosan to glyceryl stearate to benzoic acid to water ratio of 1.30:1.25:0.10:20 and then milled under the same conditions for 3 hours.

[0673] Mineral oil was added at a final ratio of chitosan to glyceryl stearate to benzoic acid to mineral oil to water of 1.30:1.25:0.10:0.50:20, followed by milling under the same conditions for 3 hours.

[0674] The viscosity was too high to measure with the Brookfield™ Viscometer. Centrifuge Separation Test, 4000 RPM for 10 minutes: No separation.

[0675] 3) Cellulose

[0676] 3.1) Cellulose containing emulsifiers and preservatives

[0677] A cellulose suspension was produced by milling cellulose in water at 670 RPM with 50 units of 10 mm balls at a cellulose to water ratio of 1.00:20 using a 10+1 substitution method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes for a total of 3 hours. Glyceryl stearate and benzoic acid were added to create a cellulose to glyceryl stearate to benzoic acid to water ratio of 1:1.25:0.10:20, then milled under the same conditions for 3 hours.

[0678] The viscosity of the suspension is shown in Figure 51. Separation testing by centrifugation at 4000 RPM for 10 minutes showed some separation of ~1 mL.

[0679] 3.2) Cellulose containing emulsifiers and preservatives and oils

[0680] A cellulose suspension was produced by milling cellulose in water at 670 RPM with 50 units of 10 mm balls at a cellulose to water ratio of 1.00:20 using a 10+1 substitution method, where it was milled for 10 minutes, followed by a 1 minute rest, then milled in the opposite direction for 10 minutes for a total of 3 hours. Glyceryl stearate and benzoic acid were added to create a cellulose to glyceryl stearate to benzoic acid to water ratio of 1:1.25:0.10:20, then milled under the same conditions for 3 hours.

[0681] Mineral oil was added at a final ratio of cellulose to glyceryl stearate to benzoic acid to mineral oil to water of 1:1.25:0.10:0.50:20, then milled under the same conditions for 3 hours.

[0682] The viscosity of the suspension is shown in Figure 51. Separation testing by centrifugation at 4000 RPM for 10 minutes revealed some separation of ~3 mL.

[0683] conclusion

[0684] The inclusion of emulsifiers and preservatives in the formulations resulted in stable chitin, chitosan and cellulose formulations. The additional inclusion of oil also produced stable formulations for all three biopolymers. Based on the results of the centrifugation separation tests, it appears that the chitosan formulation showed the highest stability, while separation was observed for the chitin (to a lesser extent) and cellulose (to a more severe extent) formulations.

[0685] [Example 28: Scale-up to large batch size]

[0686] Chitin, chitosan and cellulose were suspended in a scaled-up process using a 1.5 L Supermill Plus™, a flow-through horizontal mill.

[0687] Typical milling conditions were a rotational speed of 2400 FPM (feet per minute) with a pump flow rate of 7.3 GPH (gallons per hour) using 1.4-1.7 mm zirconia beads in 982 mL to process 20 L of slurry at 5% solids (1.05:20).

[0688] Chitin, chitosan and cellulose were successfully suspended throughout the scale-up process with milling for 140 minutes to produce uniform suspensions with the viscosities reported below in Tables 59, 60, and 61.

[0689] Table 59: Viscosity of chitin after scale-up process [Table 59]

[0690] Table 60: Viscosity of chitosan after scale-up process [Table 60]

[0691] Table 61: Viscosity of cellulose after scale-up process [Table 61]

[0692] conclusion

[0693] The horizontal media mill is capable of producing useful suspensions of biopolymers and demonstrates successful scale-up conversion resulting in high viscosity suspensions.

[0694] Headings are included herein for reference and to aid in locating particular sections. These headings are not intended to limit the scope of the concepts described therein, and these concepts may be applicable to other sections throughout the specification. Thus, the present invention is not intended to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

[0695] The singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to a "biopolymer" includes one or more of such biopolymers, and reference to "the method" includes reference to equivalent steps and methods known to those of skill in the art that may modify or substitute for the methods described herein.

[0696] Unless otherwise indicated, all numbers expressing amounts of ingredients, reaction conditions, concentrations, properties, and the like used in the specification and claims should be understood to be modified in all instances by the term "about". At the very least, each numerical parameter should be construed in light of the number of reported significant digits and by applying ordinary rounding techniques. Thus, unless indicated to the contrary, the numerical parameters set forth in the specification and appended claims are approximations that may vary depending on the properties sought to be obtained. Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the embodiments are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical values, however, inherently contain certain errors resulting from variations in experiments, testing measurements, statistical analyses and the like.

[0697] It is understood that the examples and embodiments described herein are for illustrative purposes only and that various modifications or changes in light thereof will be suggested to those skilled in the art and are included within the scope of the present invention and the appended claims.

Claims

1. comprising a stable homogenous suspension of insoluble and / or semi-soluble biopolymers in a polar solvent; Biopolymer compositions.

2. The insoluble biopolymer is selected from the group consisting of chitin, chitosan, cellulose, hemicellulose, lignin, amylose, actin, fibrin, collagen, silk, fibroin, keratin, wool, alginic acid, and mixtures thereof; The biopolymer composition of claim 1 .

3. The polar solvent is selected from the group consisting of water, ethanol, propanol, methanol, glycerin, isopropanol, acetic acid, and mixtures thereof. The biopolymer composition of claim 1 or claim 2.

4. the stable homogenous suspension comprises biopolymer fibers; the biopolymer fibres have a width of at least 10 nm, or at least 20 nm, or at least 30 nm, or at least 40 nm, or at least 50 nm, or at least 75 nm, or at least 100 nm, or at least 250 nm, or at least 500 nm, or at least 750 nm, or at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm, or at least 10 μm or greater; the biopolymer fibers have a length of about 50 nm to about 10 μm, or about 100 nm to about 10 μm, or about 500 nm to about 10 μm, or about 750 nm to about 10 μm, or about 800 nm to about 10 μm, or about 900 nm to about 5 μm, or about 1 μm to about 10 μm, or about 1 μm to about 5 μm, or about 1 μm to about 3 μm; A biopolymer composition according to any one of claims 1 to 3.

5. The stable homogenous suspension is (i) a biopolymer fiber having a spherical shape; and (ii) spheroids comprising an average effective diameter as defined in Table 3, and / or an average diameter in strength units as defined in Table 3, and / or an average diameter in volume units as defined in Table 3, and / or an average diameter in number units as defined in Table 3; At least one of A biopolymer composition according to any one of claims 1 to 4.

6. The stable homogenous suspension comprises a particle size range as defined in Table 4, or as defined in any one of Tables 30-34, as measured by SEM. A biopolymer composition according to any one of claims 1 to 5. (i) particles of cellulose having an average size of about 50 nm to about 80 nm; (ii) particles of chitin having an average size of about 45 nm to about 85 nm; (iii) particles of chitosan having an average size of about 75 nm to about 120 nm; and (iv) silk particles having an average size of about 40 nm to about 165 nm; At least one of The biopolymer composition of claim 1 or claim 2.

8. the biopolymer composition comprises a viscosity of about 20 mPa·s to about 100,000 mPa·s, or about 20 mPa·s to about 500 mPa·s, or about 1,000 mPa·s to about 40,000 mPa·s, or about 500 mPa·s to about 2,000 mPa·s, or about 1,500 mPa·s to about 30,000 mPa·s, or about 20,000 mPa·s to about 50,000 mPa·s, or about 40,000 mPa·s to about 100,000 mPa·s; A biopolymer composition according to any one of claims 1 to 7.

9. the biopolymer composition consists essentially of the biopolymer and water; A biopolymer composition according to any one of claims 1 to 8.

10. the biopolymer composition is substantially free of any added acid, any added base, any added reactive chemicals, and / or any added salts; A biopolymer composition according to any one of claims 1 to 9.

11. the biopolymer composition is obtained by a process selected from the group consisting of mechanical shearing, shear thinning, ball milling, and colloid milling; A biopolymer composition according to any one of claims 1 to 10.

12. Further comprising at least one preservative. The biopolymer composition of claim 4.

13. A cosmetic composition comprising the biopolymer composition according to any one of claims 1 to 12, the cosmetic composition is formulated as a paste, ointment, cream, lotion, gel, or milk; and The cosmetic composition preferably exhibits anti-aging and / or UV blocking properties.

14. A mechanical process for obtaining a biopolymer composition according to any one of claims 1 to 12, comprising: subjecting an insoluble and / or semi-soluble biopolymer to mechanical energy in the presence of a polar solvent to obtain a stable uniform suspension of said insoluble and / or semi-soluble biopolymer; Mechanical process.

15. A process for obtaining a biopolymer composition according to any one of claims 1 to 12, comprising: subjecting the insoluble and / or semi-soluble biopolymer to high shear conditions in the presence of a polar solvent until a change in state is observed and a stable uniform suspension of the insoluble and / or semi-soluble biopolymer is obtained. A process for obtaining a biopolymer composition.

16. the biopolymer and polar solvent are in a weight ratio of biopolymer:solvent of about 0.25:20 to about 10:20 or about 0.5:20 to about 3:20; 16. The process of claim 14 or claim 15.

17. The method of claim 17, wherein the subjecting to mechanical energy or high shear conditions comprises at least one of mechanical shearing, shear thinning, planetary ball milling, rolling, vibratory ball milling, tumbling agitation ball milling, horizontal media milling, and colloid milling.

17. The process according to any one of claims 14 to 16.